Polyolefin catalyst component containing mesoporous material and preparation method and application thereof
By using heat-activated mesoporous materials as support and combining impregnation and spray drying techniques, the polyolefin catalyst components are prepared, which solves the problems of poor catalytic activity and particle morphology in the prior art, and achieves efficient catalytic effects and uniform particle morphology.
Patent Information
- Application Number
- CN201980068497.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-30
- Filing Date
- 2019-10-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2039-10-25
AI Technical Summary
In the prior art, it is difficult to achieve high catalytic activity, uniform particle morphology and low fine powder content at the same time during ethylene polymerization or copolymerization of ethylene and α-olefins.
Polyolefin catalyst components are prepared by thermally activated mesoporous materials, such as silicon-based mesoporous materials, as support, and by optimized impregnation and spray drying methods. The method includes thermal activation treatment under an inert atmosphere, followed by impregnation treatment with a solution containing magnesium and titanium, and finally obtaining a solid catalyst component by spray drying.
The catalytic activity of the catalyst component is improved, the molecular weight distribution and melt index of the polymer are improved, and the particle morphology of the obtained catalyst component is spherical, with uniform particle size and good fluidity.
Smart Images

Figure CN113166302B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to 201811261730.1, 201811261755.1 filed on October 26, 2018 and 201811459565.0, 201811457344.X filed on November 30, 2018, which are incorporated herein by reference in their entirety for all purposes. Technical Field
[0003] The present invention relates to the technical field of heterogeneous catalytic olefin polymerization. Specifically, the present invention relates to a method for preparing a polyolefin catalyst component, a polyolefin catalyst component prepared by the method, and an application of the polyolefin catalyst component prepared by the method in an olefin monomer polymerization reaction. More specifically, the present invention relates to a polyolefin catalyst component containing a mesoporous material, a preparation method thereof, and an application thereof. Background Art
[0004] At present, the Ti-Mg Ziegler-Natta catalyst system is widely used in ethylene polymerization or copolymerization of ethylene and α-olefins. People are still conducting a lot of research. On the one hand, it is expected that the catalyst obtained has a sufficiently high polymerization activity, so that the catalyst has a high efficiency on the device and the residue in the polymer is as little as possible; on the other hand, it is hoped that the obtained polymer particles are evenly distributed, the particle morphology is as spherical as possible, and the content of polymer fine powder is small, so as to facilitate the long-term continuous operation of the industrial device. In order to obtain a good particle morphology, technicians often use a loading method to prepare the catalyst, for example, impregnating the catalytically active component on a particle carrier material, such as a porous inorganic carrier material such as silica or an organic particle carrier material. For example, US4293673, US4303771, US4302565, US4302566, and EP0835887A2 disclose the preparation of catalysts by loading magnesium compounds and titanium compounds on inorganic carriers. In such a method, the morphology of the carrier will determine the morphology of the final catalyst, and therefore such a method has high requirements on the morphology and surface properties of the carrier, resulting in an increase in the cost of catalyst preparation. In addition, the disadvantage of supported catalysts is that the impregnation step may lead to uneven loading of active components on the support surface. At the same time, due to the limitation of the specific surface area of the support, the loading amount is limited, thereby limiting the improvement of catalyst activity.
[0005] US 5,290,745 discloses a process for preparing a catalyst component suitable for producing ethylene copolymers wherein a slurry of a solution of a titanium trichloride component and magnesium dichloride in an electron donor solvent is combined with a solid particulate filler such as fumed silica and spray dried to provide a solid catalyst component.
[0006] Although a large number of documents disclose the use of porous inorganic oxide materials in the preparation of polyolefin catalyst components, the prior art has not disclosed the use of mesoporous materials such as silicon-based mesoporous materials in the preparation of polyolefin catalyst components.
[0007] There remains a need to provide polyolefin catalyst components having high catalytic activity and good particle morphology. SUMMARY OF THE INVENTION
[0009] In order to overcome the problems encountered in the prior art, the inventors have conducted diligent research. As a result, it was found that by using a mesoporous material with a high specific surface area and a relatively narrow pore size distribution, such as a silicon-based mesoporous material, as a carrier (or filler), and by an optimized preparation method, a polyolefin catalyst component showing desired performance, especially high catalytic activity, can be provided, thereby completing the present invention.
[0010] Therefore, one object of the present invention is to provide a thermally activated mesoporous material, wherein the thermal activation treatment of the mesoporous material is carried out at a temperature of 300-900° C. for a period of 3-48 h under an inert atmosphere.
[0011] Another object of the present invention is to provide a method for preparing a polyolefin catalyst component, the method comprising the steps of:
[0012] (i) providing a mesoporous material carrier that has been subjected to heat activation treatment, wherein the heat activation treatment of the mesoporous material is performed at a temperature of 300-900° C. for a period of 3-48 hours under an inert atmosphere;
[0013] (ii) under an inert atmosphere, the heat-activated mesoporous material carrier (iia) is impregnated with a solution containing a magnesium component and then with a solution containing a titanium component, (iib) is impregnated with a solution containing a titanium component and then with a solution containing a magnesium component, or (iic) is co-impregnated with solutions containing both a titanium component and a magnesium component to obtain a slurry to be sprayed; and
[0014] (iii) spray-drying the slurry to be sprayed obtained in step (ii) to obtain a solid polyolefin catalyst component.
[0015] Another object of the present invention is to provide a polyolefin catalyst component, which comprises a mesoporous material support treated by thermal activation and a magnesium component, a titanium component and an optional electron donor component supported on the support.
[0016] Another object of the present invention is to provide an olefin polymerization process, which comprises: a) polymerizing olefin monomers under polymerization conditions in the presence of the polyolefin catalyst component of the present invention and a cocatalyst to provide polyolefins; and b) recovering the polyolefins.
[0017] The inventors have found in their research that using a mesoporous material as a carrier of a polyolefin catalyst component and preparing the polyolefin catalyst component by an optimized method can effectively increase the loading amount of the active components of the catalyst component, thereby improving the catalytic activity of the obtained polyolefin catalyst component, and when the polyolefin catalyst component is used in an olefin polymerization reaction, the molecular weight distribution and melt index of the obtained polyolefin product are further improved, and the obtained polyolefin powder product is spherical and has a uniform particle size.
[0018] In addition, the method for preparing a polyolefin catalyst component of the present invention can directly obtain a spherical polyolefin catalyst component in one step by a spray drying method, and the operation is simple. The obtained spherical polyolefin catalyst component has a stable particle structure, high strength and is not easy to break, and the particle size is easy to adjust, the particle size distribution is uniform, the particle size distribution curve is narrow, and the fluidity is good.
[0019] Other features and advantages of the present invention will be described in detail below.
[0020] BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0022] Figure 1 is the XRD spectrum of the eggshell-like mesoporous material A1 of Example 1;
[0023] Figure 2A is a pore size distribution curve diagram of the eggshell-shaped mesoporous material A1 of Example 1;
[0024] Figure 2B is the nitrogen adsorption-desorption isotherm of the eggshell-shaped mesoporous material A1 of Example 1;
[0025] Figure 3A is a scanning electron microscope image of the eggshell-like mesoporous material A1 of Example 1 (magnification 500K);
[0026] Figure 3B is a scanning electron microscope image of the eggshell-shaped mesoporous material A1 of Example 1 (magnification 3000K);
[0027] Figure 4 is a scanning electron microscope image of the polyolefin catalyst Cat-1 of Example 1;
[0028] Figure 5 is the X-ray diffraction (XRD) spectrum of the spherical mesoporous silica A6 of Example 6;
[0029] Figure 6 is a scanning electron microscope image of the spherical mesoporous silica A6 of Example 6;
[0030] Figure 7 is a scanning electron microscope image of the polyolefin catalyst Cat-6 prepared in Example 6;
[0031] Figure 8 is the X-ray diffraction pattern of the mesoporous molecular sieve of Example 11;
[0032] Fig. 9 is a scanning electron microscope image of the polyolefin catalyst component prepared in Example 11;
[0033] Fig.10 is the X-ray diffraction pattern of the hexagonal mesoporous material carrier of Example 16;
[0034] Fig.11A is a nitrogen adsorption-desorption curve diagram of the hexagonal mesoporous material carrier of Example 16;
[0035] Fig. 11B is a pore size distribution diagram of the hexagonal mesoporous material carrier of Example 16;
[0036] Fig.12 is a transmission electron microscope image of the hexagonal mesoporous material carrier of Example 16;
[0037] Fig.13 is a scanning electron microscope image of the hexagonal mesoporous material carrier of Example 16;
[0038] Fig.14 This is a scanning electron microscope image of the polyolefin catalyst prepared in Example 16.
[0039] DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values therebetween, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0041] The term "mesoporous material" as used herein refers to a class of porous materials with pore sizes between 2 and 50 nm. Mesoporous materials generally have extremely high specific surface areas, regular and orderly pore structures, and narrow pore size distributions. The mesoporous material preferably has an average pore size of about 2 to about 30 nm, more preferably about 2 to about 20 nm.
[0042] As used herein, the term "polymerization" includes homopolymerization and copolymerization. As used herein, the term "polymer" includes homopolymers, copolymers and terpolymers.
[0043] The term "catalyst component" as used herein refers to the main catalyst component or procatalyst which, together with a conventional cocatalyst such as an aluminum alkyl and optionally an external electron donor, constitutes a catalyst for olefin polymerization.
[0044] As used herein, the term "halogen" refers to fluorine, chlorine, bromine and iodine.
[0045] In this document, unless otherwise specified, the average particle size of the material is measured by a laser particle size distribution instrument, and the specific surface area, pore volume and average pore size are measured according to the nitrogen adsorption method. In this document, unless otherwise specified, the particle size refers to the particle size of the granular material, wherein when the granular material is a sphere, the particle size is expressed by the diameter of the sphere, when the granular material is a cube, the particle size is expressed by the side length of the cube, and when the granular material is an irregular shape, the particle size is expressed by the mesh size of the sieve that can just sieve out the granular material.
[0046] In a first aspect, the present invention provides a heat-activated mesoporous material, wherein the heat-activated mesoporous material is subjected to a heat-activated treatment at a temperature of 300-900° C. for a period of 3-48 hours under an inert atmosphere. As mentioned above, the heat-activated mesoporous material of the present invention is suitable for use in the preparation of olefin polymerization catalyst components to provide novel olefin polymerization catalyst components having desired properties.
[0047] The heat-activated mesoporous material of the present invention can be obtained by heat-activating the mesoporous material. In principle, there is no particular limitation on the mesoporous material that can be used in the present invention. However, preferably, the mesoporous material is a mesoporous silica granular material. In some embodiments, the mesoporous material before heat activation treatment is selected from the group consisting of:
[0048] a) Mesoporous materials with a two-dimensional hexagonal pore structure, with an average pore size of 4-15 nm, 550-650 nm 2 / g specific surface area, 0.5-1.5mL / g pore volume, and 0.5-15μm average particle size;
[0049] b) Eggshell-like mesoporous materials with a two-dimensional hexagonal pore structure, which have a pore volume of 0.5-1.5 mL / g and a pore volume of 100-500 m 2 / g specific surface area, 5-15nm average pore size, and 3-20μm average particle size;
[0050] c) Spherical mesoporous silica with a cubic center structure having an average particle size of 2-9 μm, 700-900 μm 2 / g specific surface area, 0.5-1mL / g pore volume, and 1-5nm average pore diameter; and
[0051] d) a hexagonal mesoporous material having a cubic cage-like pore structure, wherein the crystal structure has a cubic-centered Im3m structure, and the average pore size of the hexagonal mesoporous material carrier is 4-15 nm, and the specific surface area is 450-550 m 2 / g, the pore volume is 0.5-1.5mL / g, and the average particle size is 0.5-10μm.
[0052] The mesoporous materials before thermal activation which can be used in the present invention are known in the art and can be prepared by methods known per se.
[0053] In some embodiments, the mesoporous material can be prepared by a method comprising the following steps:
[0054] (a) providing a crystallization mixture comprising a silicon source and a template;
[0055] (b) subjecting the crystallization mixture to crystallization conditions to form a mesoporous material; and
[0056] (c) recovering the mesoporous material.
[0057] Examples of useful silicon sources include, but are not limited to, ethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, sodium orthosilicate, and silica sol, more preferably methyl orthosilicate or ethyl orthosilicate.
[0058] In some specific embodiments, the mesoporous material can be prepared by a method (1) comprising the following steps:
[0059] (1a) under solution conditions, mixing and contacting a template with trimethylpentane and tetramethoxysilane as a silicon source to obtain a solution A;
[0060] (1b) subjecting the solution A to crystallization conditions to provide a mixture containing raw powder of eggshell-like mesoporous material;
[0061] (1c) filtering and drying the mixture obtained from step (1b) to obtain raw powder of eggshell-like mesoporous material; and
[0062] (1d) treating the eggshell-shaped mesoporous material raw powder with a template release agent.
[0063] According to the present invention, in step (1a), the conditions for the mixed contact include: temperature of 10-60°C, time of 0.2-100h, and pH of 1-6. The pH value can be formed, for example, by adding hydrochloric acid, or by using a suitable buffer system. In order to facilitate uniform mixing of the various substances, according to a preferred embodiment of the present invention, the mixed contact is carried out under stirring conditions.
[0064] According to the present invention, in step (1a), the solution condition may be an aqueous solution condition. Preferably, in order to facilitate the dissolution of the template, a buffer solution of acetic acid and sodium acetate with a pH value of 1-6 may be used to form the solution condition, and an alcohol reagent (e.g., methanol, ethanol, n-propanol, isopropanol, etc.) may be added.
[0065] Preferably, the weight ratio of the template, the trimethylpentane and the tetramethoxysilane is 1:(1.2-20):(0.1-15); more preferably 1:(2-12):(0.5-10).
[0066] According to the present invention, in step (1a), the template is preferably selected so that the obtained eggshell-like mesoporous material powder has a two-dimensional hexagonal pore distribution structure. Preferably, the template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene, such as EO 20 PO 70 EO 20 (It can be purchased from Aldrich Company with the trade name P123). When the template is polyoxyethylene-polyoxypropylene-polyoxyethylene, the molar number of the template is calculated based on the average molecular weight of polyoxyethylene-polyoxypropylene-polyoxyethylene.
[0067] Preferably, in step (1b), the crystallization conditions include: temperature of 30-150° C. and time of 4-72 hours. According to a preferred embodiment, the crystallization is performed by a hydrothermal crystallization method.
[0068] Preferably, in step (1c), the filtering process may include: after filtering, repeatedly washing with deionized water (the number of washing times may be 2-10), and then performing suction filtration.
[0069] Preferably, in step (1c), the drying can be carried out in a drying oven. The drying conditions may include: a temperature of 110-150° C. and a time of 3-6 hours.
[0070] According to a preferred embodiment of the present invention, in step (1a), the method for carrying out the mixed contact comprises: firstly bringing the template into first contact with trimethylpentane under solution conditions; and then bringing the mixture obtained after the first contact into second contact with tetramethoxysilane. Preferably, the conditions for the first contact comprise: temperature of 10-60°C, time of 0.1-20h, and pH value of 1-6. Preferably, the conditions for the second contact comprise: temperature of 10-60°C, time of 0.1-80h, and pH value of 1-6.
[0071] According to the present invention, in step (1d), the process of removing the template treatment includes: calcining the eggshell-shaped mesoporous material raw powder at 300-600°C; preferably, the calcination time is 8-36 hours, preferably 8-20 hours.
[0072] Alternatively, in step (1d), the method for removing the template agent treatment is an alcohol washing method. For example, the process of removing the template agent treatment includes: washing the mesoporous material raw powder with alcohol at a temperature of 50-120° C., such as 70-120° C. or 90-120° C., for 10-40 hours. Examples of useful alcohols include, but are not limited to, ethanol, propanol, isopropanol, n-butanol, and 2-butanol.
[0073] In some specific embodiments, the mesoporous material can be prepared by a method (2) comprising the following steps:
[0074] (2a) mixing and contacting a silicon source and an acid agent in the presence of a template agent to provide a crystallization mixture;
[0075] (2b) subjecting the crystallization mixture to crystallization conditions to provide a mixture comprising raw powder of a mesoporous material having a cubic centered structure;
[0076] (2c) filtering and drying the mixture obtained in step (2b) to obtain a raw powder of a mesoporous material having a cubic core structure; and
[0077] (2d) treating the raw powder of the mesoporous material having a cube-centered structure with a template release agent.
[0078] In the method (2) of the present invention, the type of the template is not particularly limited, as long as the mesoporous material powder obtained can have a cubic core structure. Preferably, the template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene, such as EO 106 PO 70 EO 106 (It can be purchased from Aldrich Company, trade name F127, number average molecular weight Mn is 12600). When the template is polyoxyethylene-polyoxypropylene-polyoxyethylene, the molar number of the template is calculated according to the average molecular weight of polyoxyethylene-polyoxypropylene-polyoxyethylene.
[0079] According to the present invention, the acid agent may be any acidic aqueous solution conventionally used in the art, for example, an aqueous solution of at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrobromic acid, preferably an aqueous solution of hydrochloric acid.
[0080] The amount of the acid agent used is not particularly limited and can vary within a wide range, preferably making the pH value of the mixed contact range from 1 to 6.
[0081] Preferably, in step (2a), the contact conditions include: temperature of 10-60°C, preferably 25-60°C, time of more than 25 min, and pH of 1-6. In order to facilitate uniform mixing of the substances, according to a preferred embodiment of the present invention, the mixed contact is carried out under stirring conditions.
[0082] In the present invention, the amount of the template and the silicon source can vary within a wide range, for example, the molar ratio of the template to the silicon source can be 1:200-300; preferably 1:225-275.
[0083] In the method (2) of the present invention, the silicon source can be various silicon sources conventionally used in the art. Preferably, the silicon source is at least one of ethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, sodium orthosilicate and silica sol, and more preferably methyl orthosilicate or ethyl orthosilicate.
[0084] According to a preferred embodiment of the present invention, the process of mixing and contacting the silicon source with the acid agent in the presence of a template agent comprises: adding the template agent triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene F127 to an aqueous solution of hydrochloric acid, with a molar feed ratio of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene F127: water: hydrogen chloride = 1: 9000-15000: 100-500, stirring at a temperature of 25-60°C until dissolved, and then adding silicon source tetraethyl orthosilicate to the above-mentioned solution, with the amount of tetraethyl orthosilicate used being a molar feed ratio of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene F127: tetraethyl orthosilicate = 1: 225-275, and stirring at a temperature of 25-60°C for more than 25 minutes.
[0085] According to the present invention, the crystallization conditions may include: temperature of 30-150°C, time of 10-72h, preferably, the crystallization conditions include: temperature of 90-120°C, time of 10-40h. According to a preferred embodiment, the crystallization is carried out by hydrothermal crystallization.
[0086] The operation of recovering the raw powder of the mesoporous material having a cubic core structure (including filtering, drying and template removal treatment) is as described above for method (1).
[0087] In some specific embodiments, the mesoporous material can be prepared by a method (3) comprising the following steps:
[0088] (3a) mixing and contacting a silicon source and an acid agent in the presence of a template agent to provide a crystallization mixture;
[0089] (3b) subjecting the crystallization mixture to crystallization conditions to provide a mixture containing raw powder of a mesoporous material having a two-dimensional hexagonal pore structure;
[0090] (3c) filtering and drying the mixture containing the raw mesoporous material powder having a two-dimensional hexagonal pore structure to obtain raw mesoporous material powder; and
[0091] (3d) treating the raw powder of the mesoporous material with a template release agent.
[0092] According to the present invention, in step (3a), the type of the template is not particularly limited, as long as the obtained mesoporous material powder has a two-dimensional hexagonal pore structure. Preferably, the template can be a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene, such as EO 20 PO 70 EO 20 (It can be purchased from Aldrich Company with the trade name P123). When the template is polyoxyethylene-polyoxypropylene-polyoxyethylene, the molar number of the template is calculated based on the average molecular weight of polyoxyethylene-polyoxypropylene-polyoxyethylene.
[0093] The acid agent may be various acidic aqueous solutions commonly used in the art, for example, an aqueous solution of at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrobromic acid, preferably an aqueous solution of hydrochloric acid.
[0094] The amount of the acid agent used is not particularly limited and can vary within a wide range, preferably making the pH value of the mixed contact range from 1 to 6.
[0095] Preferably, in step (3a), the mixing contact conditions include: temperature of 25-60°C, time of more than 25 min, and pH of 1-6. In order to facilitate uniform mixing of the substances, according to a preferred embodiment of the present invention, the mixing contact is carried out under stirring conditions.
[0096] In the method (3) of the present invention, the amount of the template and the silicon source can vary within a wide range, for example, the molar ratio of the template to the silicon source can be 1:10-90; preferably 1:50-75.
[0097] In the method (3) of the present invention, the silicon source can be various silicon sources conventionally used in the art. Preferably, the silicon source is at least one of ethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, sodium orthosilicate and silica sol, and more preferably methyl orthosilicate or ethyl orthosilicate.
[0098] According to a preferred embodiment of the present invention, the process of mixing and contacting the silicon source with the acid agent in the presence of a template agent comprises: adding the template agent triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene P123 to an aqueous solution of hydrochloric acid, with a molar feed ratio of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene P123: water: hydrogen chloride = 1: 9000-15000: 100-500, stirring at a temperature of 25-60°C until dissolved, and then adding silicon source tetraethyl orthosilicate to the above-mentioned solution, with the amount of tetraethyl orthosilicate used being a molar feed ratio of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene P123: tetraethyl orthosilicate = 1: 50-75, and stirring at a temperature of 25-60°C for more than 25 minutes.
[0099] Preferably, the crystallization conditions include: a temperature of 90-180°C and a time of 10-40 hours. According to a preferred embodiment, the crystallization is carried out by a hydrothermal crystallization method. In order to ensure that a mesoporous molecular sieve material with a sufficiently large pore size can be obtained, the crystallization conditions are further preferably a temperature of 130-180°C.
[0100] The operation of recovering the raw powder of the mesoporous material having a two-dimensional hexagonal pore structure (including filtering, drying and template removal treatment) is as described above for method (1).
[0101] In some specific embodiments, the mesoporous material can be prepared by a method (4) comprising the following steps:
[0102] (4a) mixing and contacting a template, potassium sulfate, an acid agent, and a silicon source to provide a crystallization mixture;
[0103] (4b) subjecting the crystallization mixture to crystallization conditions to provide a mixture containing raw powder of hexagonal mesoporous material having a cube-centered Im3m structure;
[0104] (4c) filtering and drying to obtain a hexagonal mesoporous material powder having a cubic center Im3m structure; and
[0105] (4d) treating the raw powder of the hexagonal mesoporous material with a template release agent.
[0106] In the method (4) of the present invention, the silicon source can be various silicon sources conventionally used in the art. Preferably, the silicon source is at least one of ethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, sodium orthosilicate and silica sol, and more preferably methyl orthosilicate or ethyl orthosilicate.
[0107] According to some preferred embodiments of the present invention, the process of preparing the hexagonal mesoporous material raw powder with a cubic center Im3m structure may include: mixing and contacting a template, potassium sulfate, an acid agent and a silicon source such as tetraethyl orthosilicate, and crystallizing, filtering and drying the obtained mixture. There is no particular limitation on the order of the mixed contact, and the template, potassium sulfate, acid agent and silicon source can be mixed at the same time, or any two or three can be mixed, and then other components are added and mixed evenly. According to a preferred embodiment, the template, potassium sulfate and acid agent are first mixed evenly, and then a silicon source such as tetraethyl orthosilicate is added and mixed evenly.
[0108] In the method (4) of the present invention, the amount of the template, potassium sulfate and silicon source such as tetraethyl orthosilicate can vary within a wide range. For example, the molar ratio of the template, potassium sulfate and silicon source such as tetraethyl orthosilicate can be 1:100-800:20-200, preferably 1:150-700:80-180, and more preferably 1:200-400:100-150.
[0109] In the method (4) of the present invention, the template agent may be any conventional template agent in the art. For example, the template agent may be a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene, such as Synperonic F108 (available from Fuka Corporation, with a molecular formula of EO 132 PO 60 EO 132 , average molecular weight M n =14600). The number of moles of polyoxyethylene-polyoxypropylene-polyoxyethylene is calculated based on the average molecular weight of polyoxyethylene-polyoxypropylene-polyoxyethylene.
[0110] In the method (4) of the present invention, the acid agent may be any acidic aqueous solution conventionally used in the art, for example, an aqueous solution of at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrobromic acid, preferably an aqueous solution of hydrochloric acid.
[0111] The amount of the acid agent used is not particularly limited and can vary within a wide range, preferably making the pH value of the mixture 1-7.
[0112] The present invention has no particular limitation on the conditions of the mixed contact. For example, the mixed contact conditions may include: a temperature of 25-60°C, a time of 10-240 min, and a pH value of 1-7. In order to facilitate uniform mixing of the various substances, according to a preferred embodiment of the present invention, the mixed contact is carried out under stirring conditions.
[0113] According to a preferred embodiment of the present invention, the process of mixing and contacting the template, potassium sulfate, acid and silicon source such as tetraethyl orthosilicate comprises: adding the template triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene F108 to an aqueous solution of hydrochloric acid, with a molar feed ratio of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene F108: potassium sulfate: water: hydrogen chloride = 1: 200-400: 10000-30000: 100-900, stirring at a temperature of 25-60°C until dissolved, and then adding a silicon source such as tetraethyl orthosilicate to the above-mentioned solution, with the amount of the silicon source being used in a molar feed ratio of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene F108: silicon source = 1: 100-150, and stirring at a temperature of 25-60°C for 10-240 minutes.
[0114] In the method (4) of the present invention, the crystallization conditions are not particularly limited. For example, the crystallization conditions may include: a temperature of 25-100°C, preferably 25-60°C, more preferably 30-55°C; a time of 10-72h, preferably 10-40h. According to a preferred embodiment, the crystallization is carried out by a hydrothermal crystallization method.
[0115] The operation of recovering the raw powder of the hexagonal mesoporous material having a cube-centered Im3m structure (including filtration, drying and template removal treatment) is as described above for method (1).
[0116] According to the present invention, before the mesoporous material is used for the preparation of the catalyst component, in order to remove the hydroxyl groups and residual water on the surface of the mesoporous material, the mesoporous material needs to be subjected to a thermal activation treatment. The conditions of the thermal activation treatment may include: calcining the mesoporous material at a temperature of 300-900° C. for 3-48 hours, preferably 3-24 hours, and more preferably 7-10 hours in an inert atmosphere such as a nitrogen or argon atmosphere.
[0117] In some embodiments, the heat-activated mesoporous material of the present invention may be further treated with a chlorosilane. Examples of useful chlorosilanes include, but are not limited to, dichlorodimethoxysilane, monochlorotrimethoxysilane, dichlorodiethoxysilane, and monochlorotriethoxysilane.
[0118] The chlorosilane treatment can be accomplished by stirring or grinding the heat-activated mesoporous material with the chlorosilane in the presence or absence of other media such as an inert solvent, and the treatment temperature can be in the range of 20-150°C, preferably in the range of 30-120°C, and more preferably in the range of 40-100°C.
[0119] Conveniently, the treatment with the chlorosilane can be carried out simultaneously with the ball milling treatment described below, that is, the chlorosilane is added to the heat-activated mesoporous material in the ball milling jar before or during the ball milling treatment.
[0120] The mesoporous material treated with chlorosilane of the present invention has a contact angle of at least 40°, preferably 50-150°, more preferably 60-140°, still more preferably 70-130°.
[0121] In a second aspect, the present invention provides a method for preparing a polyolefin catalyst component, the method comprising the steps of:
[0122] (i) providing a heat-activated mesoporous material, wherein the heat activation treatment of the mesoporous material is carried out at a temperature of 300-900° C. under an inert atmosphere for 3-48 h, preferably 3-24 h, more preferably 7-10 h;
[0123] (ii) in an inert atmosphere, the heat-activated mesoporous material (iia) is impregnated with a solution containing a magnesium component and then with a solution containing a titanium component, (iib) is impregnated with a solution containing a titanium component and then with a solution containing a magnesium component, or (iic) is co-impregnated with solutions containing both a titanium component and a magnesium component to obtain a slurry to be sprayed, and
[0124] (iii) spray-drying the slurry to be sprayed obtained in step (ii) to obtain a solid polyolefin catalyst component.
[0125] In some embodiments, the method further comprises: before step (ii), treating the heat-activated mesoporous material with chlorosilane, and / or ball-milling the heat-activated mesoporous material.
[0126] In some embodiments, the chlorine-containing silane is selected from the group consisting of dichlorodimethoxysilane, monochlorotrimethoxysilane, dichlorodiethoxysilane, and monochlorotriethoxysilane.
[0127] The operation of treating with chlorosilane is as described above. In some embodiments, the treatment of the heat-activated mesoporous material with chlorosilane is performed as follows: under an inert atmosphere, the heat-activated mesoporous material and chlorosilane are ball-milled together in a ball mill.
[0128] In the present invention, the specific operation method and conditions of the ball milling treatment are based on not destroying or substantially not destroying the pore structure of the mesoporous material. Those skilled in the art can select various suitable conditions to implement the present invention according to the above principles. Specifically, the ball milling treatment can be carried out in a ball mill. The diameter of the grinding balls in the ball mill can be 2-80mm, or 2-50mm, or 2-30mm, or 2-20mm, or 3-15mm, such as 2-3mm or 3-5mm. The grinding balls in the ball mill can have the same or different diameters. Usually, the grinding balls in the ball mill have different diameters, among which the number ratio of large balls (diameter greater than two-thirds of (maximum diameter-minimum diameter)), medium balls (diameter between two-thirds and one-third of (maximum diameter-minimum diameter)) and small balls (diameter less than one-third of (maximum diameter-minimum diameter)) can be approximately 1:2:3. The number of grinding balls can be reasonably selected according to the size of the ball mill, for example, a ball mill of 50-150 mL can usually use 20-80 grinding balls; the material of the grinding balls can be agate, polytetrafluoroethylene, etc., preferably agate. The conditions for the ball milling include: the rotation speed of the ball mill can be 100-800r / min, preferably 200-700r / min, more preferably 300-500r / min, the temperature in the ball mill can be 15-100°C, and the ball milling time can be 0.1-100 hours. Preferably, the conditions for the ball milling treatment are such that the average particle size of the mesoporous material obtained by ball milling is less than 10μm, for example, in the range of 0.05-5μm, preferably in the range of 0.1-3μm, and more preferably in the range of 0.1-2μm.
[0129] According to the present invention, the solution containing the magnesium component and / or the titanium component can be a solution containing the magnesium component and / or the titanium component in an organic solvent, and the organic solvent can be an electron donor solvent, for example, at least one selected from alkyl esters of aliphatic or aromatic carboxylic acids, aliphatic ethers and cyclic ethers, preferably at least one of C1-C4 alkyl esters of C1-C4 saturated aliphatic carboxylic acids, alkyl esters of C7-C8 aromatic carboxylic acids, C2-C6 aliphatic ethers and C3-C4 cyclic ethers; more preferably at least one of methyl formate, ethyl formate, methyl acetate, ethyl acetate, butyl acetate, ethyl ether, hexyl ether and tetrahydrofuran (THF); further preferably tetrahydrofuran.
[0130] According to the present invention, the mesoporous material can be loaded with magnesium component and / or titanium component by impregnation, and the capillary pressure of the pore structure of the carrier is relied on to make the magnesium component and / or titanium component enter the pores of the mesoporous material, and at the same time, the magnesium component and / or titanium component will also be adsorbed on the surface of the mesoporous material until the magnesium component and / or titanium component reach adsorption equilibrium on the surface of the mesoporous material. The impregnation treatment can be a co-impregnation treatment or a step-by-step impregnation treatment. In order to save preparation costs and simplify the experimental process, the impregnation treatment is preferably a co-impregnation treatment. Preferably, the conditions of the impregnation treatment may include: an impregnation temperature of 25-100°C, preferably 40-80°C; an impregnation time of 0.1-5h, preferably 1-4h.
[0131] According to the present invention, the amount of the mesoporous material, the magnesium component and the titanium component is preferably such that in the prepared polyolefin catalyst component, based on the total weight of the polyolefin catalyst component, the content of the mesoporous material is 20-90% by weight, preferably 30-70% by weight, the content of the magnesium component in terms of magnesium element is 1-50% by weight, preferably 1-30% by weight, more preferably 2-25% by weight, still more preferably 3-20% by weight, the content of the titanium component in terms of titanium element is 1-50% by weight, preferably 1-30% by weight, more preferably 1-10% by weight, still more preferably 1-5% by weight. The sum of the contents of the magnesium component and the titanium component (in terms of element) is preferably 10-30% by weight, based on the total weight of the polyolefin catalyst component.
[0132] Preferably, in step (ii), the weight ratio of the mesoporous material and the solution containing the magnesium component and / or the titanium component may be 1:50-150, preferably 1:75-120.
[0133] Preferably, in step (ii), the amounts of the magnesium component and the titanium component are such that in the prepared polyolefin catalyst component, the molar ratio of the magnesium component calculated as magnesium element to the titanium component calculated as titanium element is 0.5-50:1, preferably 2-30:1, more preferably 5-18:1.
[0134] According to the present invention, the magnesium component may be a general formula of Mg(OR 1 ) m X 2-m A magnesium compound wherein R 1 is a hydrocarbon group having 2 to 20 carbon atoms, such as C2-C 10 alkyl, X is a halogen atom, 0≤m≤2. For example, the magnesium component may be at least one of diethoxymagnesium, dipropoxymagnesium, dibutoxymagnesium, dioctyloxymagnesium, magnesium dichloride and magnesium dibromide.
[0135] According to the present invention, the titanium component may be a general formula of Ti(OR2 ) n X 4-n A titanium compound, wherein R2 is a hydrocarbon group having 1 to 20 carbon atoms, such as C1-C 10 An alkyl group, X is a halogen atom, 0≤n≤4, and / or titanium trichloride. For example, the titanium component may be at least one of tetraethyl titanate, tetramethyl titanate, tetrabutyl titanate, tetraisopropyl titanate, titanium trichloride and titanium tetrachloride.
[0136] In some embodiments of the method of the present invention, a magnesium component precursor that can be converted into the above-mentioned magnesium component during the preparation of the catalyst component can be used to replace the magnesium component, and / or a titanium component precursor that can be converted into the above-mentioned titanium component during the preparation of the catalyst component can be used to replace the titanium component.
[0137] According to the present invention, there is no particular limitation on the concentrations of the magnesium component and the titanium component in the solution containing the magnesium component and / or the titanium component. For example, the concentrations of the magnesium component and the titanium component may be conventionally selected in the art. For example, the concentration of the magnesium component may be 0.1-1 mol / L, and the concentration of the titanium component may be 0.01-0.2 mol / L.
[0138] According to the present invention, during the impregnation process, the inert gas is a gas that does not react with the raw materials and products, for example, it can be nitrogen or at least one of the gases of the zeroth group elements in the periodic table, preferably nitrogen.
[0139] According to the present invention, the spray drying can be implemented according to conventional methods. For example, the spray drying method can be selected from at least one of pressure spray drying, centrifugal spray drying and airflow spray drying. According to a preferred embodiment of the present invention, the spray drying adopts airflow spray drying. The spray drying can be carried out in an atomizer. The conditions for the spray drying may include: under a nitrogen or argon protective atmosphere, an air inlet temperature of 100-150°C, an air outlet temperature of 100-120°C, and a carrier gas flow rate of 10-50L / s. Preferably, the conditions for the spray drying are such that the average particle size of the prepared polyolefin catalyst component is 0.5-50μm, preferably 3-25μm or 1-20μm or 0.5-20μm or 5-30μm, and the particle size distribution value ((D90-D10) / D50) is 0.7-2.0, preferably 0.8-1.8, for example 0.85-0.95 or 1.7-1.8 or 1.6-1.7.
[0140] According to a preferred embodiment of the present invention, the steps (ii)-(iii) are carried out as follows: under an inert atmosphere, in a reactor equipped with stirring, an electron donor solvent tetrahydrofuran (THE) is added, the reactor temperature is controlled to be 25-40°C, magnesium chloride and titanium tetrachloride are quickly added when stirring is turned on, and the system temperature is adjusted to 60-75°C for constant temperature reaction for 1-5 hours, until the magnesium chloride and titanium tetrachloride are completely dissolved, to obtain an organic solution containing magnesium dichloride and titanium tetrachloride. The organic solution containing magnesium dichloride and titanium tetrachloride is mixed with the mesoporous material, and the ratio between the components is controlled to be 0.5-50 moles of magnesium element relative to 1 mole of titanium element, preferably 1-10 moles, and the amount of electron donor solvent tetrahydrofuran (THE) is 0.5-200 moles, preferably 20-200 moles, and the reactor temperature is controlled to be 60-75°C, and the reaction is stirred for 0.1-5 hours to obtain a uniform concentration of the slurry to be sprayed. The amount of the mesoporous material added should be sufficient to form a slurry suitable for spray forming. Then the obtained slurry to be sprayed is introduced into a spray dryer, and under the protection of N2, the air inlet temperature of the spray dryer is controlled to be 100-150°C, the air outlet temperature is 100-120°C, and the carrier gas flow rate is 10-50L / s to obtain spherical particles with an average particle size of 0.5-50μm, preferably 3-25μm or 1-20μm or 0.5-20μm.
[0141] The following technical solutions have also been considered:
[0142] A method for preparing a polyolefin catalyst component, the method comprising the following steps:
[0143] (i) providing a heat-activated mesoporous material, wherein the heat activation treatment of the mesoporous material is performed at a temperature of 300-900° C. for a time of 3-48 hours under an inert atmosphere;
[0144] (ii) in an inert atmosphere, impregnating the heat-activated mesoporous material with a solution containing a magnesium component to obtain a slurry to be sprayed;
[0145] (iii) spray-drying the slurry to be sprayed obtained from step (ii) to obtain a composite support containing a magnesium component and a mesoporous material; and
[0146] (iv) supporting a titanium component on the composite carrier by an impregnation method to provide a solid polyolefin catalyst component.
[0147] The operation and conditions of each step of this technical solution are similar to those described above.
[0148] The polyolefin catalyst component prepared by the above method has a spherical or quasi-spherical morphology, so it is sometimes conveniently referred to as a spherical catalyst component. The term "spherical catalyst component" used herein means that the catalyst component has a spherical or quasi-spherical particle morphology, but does not require the catalyst component to have a perfect spherical morphology. The catalyst component of the present invention has a high magnesium component and titanium component loading and a reasonable pore structure. When the catalyst component of the present invention is used for the polymerization of olefin monomers, the polymerization activity is higher, the obtained polymer particles have a good morphology, a narrow molecular weight distribution, and excellent fluidity.
[0149] In a third aspect, the present invention provides a polyolefin catalyst component containing a mesoporous material prepared by the above method.
[0150] In some embodiments, the polyolefin catalyst component of the present invention comprises a heat-activated mesoporous material carrier and a magnesium component and a titanium component supported on the carrier. The mesoporous material, its heat activation treatment, ball milling treatment and optional chlorosilane treatment are as described above, and the magnesium component and the titanium component are as described above.
[0151] The polyolefin catalyst component of the present invention may further comprise an electron donor component. In some embodiments, the electron donor component is derived from the electron donor solvent present in the slurry to be sprayed.
[0152] In some embodiments, the polyolefin catalyst component of the present invention comprises a thermally activated mesoporous material, magnesium, titanium, a halogen, and an electron donor.
[0153] According to the present invention, based on the total weight of the polyolefin catalyst component, the content of the mesoporous material carrier is 20-90% by weight, preferably 30-70% by weight; the content of the magnesium component in terms of magnesium element is 1-50% by weight, preferably 1-30% by weight, more preferably 2-25% by weight, still more preferably 3-20% by weight; the content of the titanium component in terms of titanium element is 1-50% by weight, preferably 1-30% by weight, more preferably 1-10% by weight, still more preferably 1-5% by weight.
[0154] Preferably, in the polyolefin catalyst component, the molar ratio of the magnesium component (calculated as magnesium element) to the titanium component (calculated as titanium element) is 0.5-50:1, preferably 5-18:1.
[0155] In some embodiments, the polyolefin catalyst component of the present invention comprises the eggshell-like mesoporous material carrier described above. The eggshell-like mesoporous material carrier has a special cubic centered crystal structure, and its mesoporous channel structure is evenly distributed, the pore size is suitable, the pore volume is large, the mechanical strength is good, and it has good structural stability, which is particularly conducive to the good dispersion of magnesium and titanium active components on the surface of the carrier, so that the prepared polyolefin catalyst component has the advantages of a supported catalyst such as good dispersion of metal active components, high loading, few side reactions, simple post-treatment, etc., and has a strong catalytic activity, ensuring that the supported catalyst component prepared by using the eggshell-like mesoporous material carrier as a carrier has better catalytic activity in the polymerization reaction of olefin monomers, and significantly improves the conversion rate of the reaction raw materials.
[0156] According to the present invention, by controlling the structural parameters of the eggshell-like mesoporous material carrier within the above range, it can be ensured that the eggshell-like mesoporous material carrier is not easy to agglomerate, and the supported catalyst component prepared by using it as a carrier can improve the conversion rate of the reaction raw materials in the olefin polymerization reaction process. When the specific surface area of the eggshell-like mesoporous material carrier is less than 100m 2 / g and / or the pore volume is less than 0.5mL / g, the catalytic activity of the supported catalyst component prepared by using it as a carrier will be significantly reduced; when the specific surface area of the eggshell-like mesoporous material carrier is greater than 500m 2 / g and / or the pore volume is greater than 1.5mL / g, the supported catalyst prepared by using it as a carrier is prone to agglomeration during the olefin polymerization reaction, thereby affecting the conversion rate of olefin monomers in the olefin polymerization reaction.
[0157] Preferably, the eggshell-shaped mesoporous material carrier has a pore volume of 0.5-1.2 mL / g and a specific surface area of 150-350 m 2 / g, the average pore size is 7-12nm, the average particle size before ball milling is 3-20μm, the average particle size after ball milling is 0.05-5μm, preferably 0.1-3μm, more preferably 0.1-2, so that the eggshell-like mesoporous material carrier can be ensured to have the advantages of larger pore size, larger pore volume and larger specific surface area, which is more conducive to the good dispersion of magnesium and / or titanium active components on the surface of the eggshell-like mesoporous material carrier, and further ensure that the polyolefin catalyst component prepared therefrom has excellent catalytic performance, thereby obtaining the beneficial effects of high olefin monomer conversion rate and good polymer particle morphology, narrow molecular weight distribution, excellent fluidity and the like.
[0158] Preferably, the polyolefin catalyst has a pore volume of 0.5-1 mL / g and a specific surface area of 120-300 m 2 / g, the average pore size is 7-12nm, the average particle size is 3-25μm, and the particle size distribution value ((D90-D10) / D50) is 0.85-0.95.
[0159] In some embodiments, the polyolefin catalyst component of the present invention comprises a mesoporous material carrier having a cubic centered crystal structure and a magnesium component and a titanium component supported on the carrier, wherein the average particle size of the mesoporous material carrier is 0.05-5 μm, preferably 0.1-3 μm, more preferably 0.1-2 μm, and the specific surface area is 700-900 m 2 / g, the pore volume is 0.5-1mL / g, and the average pore diameter is 1-5nm.
[0160] Since the mesoporous material carrier has a special cubic centered crystal structure, its mesoporous channel structure is evenly distributed, the pore size is appropriate, the pore volume is large, the mechanical strength is good, and it has good structural stability, which is particularly conducive to the good dispersion of magnesium and titanium active components on the carrier surface. The prepared polyolefin catalyst component has the advantages of a supported catalyst component, such as good dispersion of metal active components, high loading, few side reactions, simple post-treatment, etc., and has a strong catalytic activity, ensuring that the prepared supported catalyst component has better catalytic activity when used in olefin monomer polymerization reactions, and significantly improves the conversion rate of the reaction raw materials.
[0161] According to the present invention, by controlling the structural parameters of the mesoporous material carrier having a cubic centered crystal structure within the above range, it can be ensured that the mesoporous material carrier is not prone to agglomeration, and the supported catalyst component prepared by using it as a carrier can improve the conversion rate of the reaction raw materials in the olefin polymerization reaction process. When the specific surface area of the mesoporous material carrier is less than 700 m 2 / g and / or the pore volume is less than 0.5mL / g, the catalytic activity of the supported catalyst component prepared by using it as a carrier will be significantly reduced; when the specific surface area of the mesoporous material carrier is greater than 900m 2 / g and / or the pore volume is greater than 1 mL / g, the supported catalyst component prepared by using it as a carrier is prone to agglomeration during the olefin polymerization reaction, thereby affecting the conversion rate of the olefin monomer in the olefin polymerization reaction.
[0162] Preferably, the average particle size of the mesoporous material carrier before ball milling is 3-9 μm, the average particle size after ball milling is 0.05-5 μm, preferably 0.1-3 μm, more preferably 0.1-2, and the specific surface area is 750-850 m 2 / g, the pore volume is 0.6-0.8mL / g, and the average pore size is 1.5-4.5nm, which can ensure that the mesoporous material carrier has the advantages of larger pore size, larger pore volume, and larger specific surface area, which is more conducive to the good dispersion of magnesium and titanium active components on the surface of the mesoporous material carrier, and further ensure that the polyolefin catalyst component prepared therefrom has excellent catalytic performance, thereby obtaining a high olefin monomer conversion rate and the obtained polymer particles have good morphology, narrow molecular weight distribution, excellent fluidity and other beneficial effects.
[0163] Preferably, the average particle size of the polyolefin catalyst component is 3-25 μm, and the specific surface area is 700-800 m 2 / g, the pore volume is 0.5-0.8mL / g, the average pore diameter is 1.5-4.5nm, and the particle size distribution value is 0.85-0.95.
[0164] In some embodiments, the polyolefin catalyst component of the present invention comprises a mesoporous material carrier having a two-dimensional hexagonal pore structure and a magnesium component and a titanium component supported on the carrier, wherein the average pore size of the mesoporous material carrier is 4-15 nm and the specific surface area is 550-650 m 2 / g, the pore volume is 0.5-1.5mL / g, the average particle size is 0.05-5μm, preferably 0.1-3μm, more preferably 0.1-2.
[0165] Since the mesoporous material carrier has a special two-dimensional hexagonal pore structure, which is a good long-range ordered structure, the mesoporous material exhibits high strength in a wide temperature range and a large strain state. In addition, the unique two-dimensional hexagonal pore structure of the mesoporous material, combined with its narrow pore size distribution and uniform pore distribution, is conducive to the good dispersion of the metal component on the carrier surface, so that the prepared polyolefin catalyst component has the advantages of a supported catalyst, such as good dispersibility of magnesium and titanium active components, high loading, few side reactions, simple post-processing, etc., and has strong catalytic activity and high stability, ensuring that the supported catalyst component has better catalytic activity when used in olefin monomer polymerization reaction, and significantly improves the conversion rate of reaction raw materials.
[0166] According to the present invention, by controlling the structural parameters of the mesoporous material having a two-dimensional hexagonal pore structure within the above range, it can be ensured that the mesoporous material is not prone to agglomeration, and the supported catalyst component prepared by using the mesoporous material as a carrier can improve the conversion rate of the reaction raw materials in the olefin polymerization reaction process. When the specific surface area of the mesoporous material is less than 550 m 2 / g and / or the pore volume is less than 0.5mL / g, the catalytic activity of the supported catalyst component prepared by using it as a carrier will be significantly reduced; when the specific surface area of the mesoporous material is greater than 650m 2 / g and / or the pore volume is greater than 1.5mL / g, the supported catalyst component prepared by using it as a carrier is prone to agglomeration during the olefin polymerization reaction, thereby affecting the conversion rate of olefin monomers in the olefin polymerization reaction.
[0167] Preferably, the average pore size of the mesoporous material is 4-12 nm, such as 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm and 12 nm, and any average pore size between any two average pore sizes, and the specific surface area is 580-620 m 2 / g, the pore volume is 0.5-1mL / g, the average particle size before ball milling is 0.8-10μm, and the average pore size after ball milling is 0.05-5μm, preferably 0.1-3μm, and more preferably 0.1-2, so that the mesoporous material can be ensured to have the advantages of larger pore size, larger pore volume, and larger specific surface area, which is more conducive to the good dispersion of magnesium and titanium active components on the surface of the mesoporous material, and further ensure that the polyolefin catalyst component prepared therefrom has excellent catalytic performance, thereby obtaining the beneficial effects of high olefin monomer conversion rate and good polymer particle morphology, narrow molecular weight distribution, and excellent fluidity.
[0168] Preferably, the average pore size of the polyolefin catalyst component is 4-15 nm, and the specific surface area is 520-600 m 2 / g, the pore volume is 0.6-1.4mL / g, the average particle size is 1-20μm, and the particle size distribution value is 1.7-1.8.
[0169] In some embodiments, the polyolefin catalyst component of the present invention comprises a hexagonal mesoporous material carrier having a cubic cage-like pore structure and a magnesium component and a titanium component supported on the carrier, wherein the crystal structure of the hexagonal mesoporous material has a cubic-centered 1 m3m structure, the average pore size of the hexagonal mesoporous material is 4-15 nm, and the specific surface area is 450-550 m 2 / g, the pore volume is 0.5-1.5mL / g, and the average particle size is 0.05-5μm, preferably 0.1-3μm, and more preferably 0.1-2μm.
[0170] The hexagonal mesoporous material carrier has a special Im3m cubic centered crystal structure, which is a non-closest packing mode. This good long-range ordered structure enables the hexagonal mesoporous material to exhibit high strength in a wide temperature range and under a large strain state. In addition, the unique hole structure of the hexagonal mesoporous material, combined with its narrow pore size distribution and uniform pore distribution, is conducive to the good dispersion of magnesium and titanium active components on the carrier surface, so that the prepared polyolefin catalyst component has the advantages of a supported catalyst such as good dispersibility of metal active components, high loading, few side reactions, simple post-processing, etc., and has strong catalytic activity and high stability, ensuring that the supported catalyst component has better catalytic activity in the polymerization reaction of olefin monomers and significantly improves the conversion rate of the reaction raw materials.
[0171] According to the present invention, by controlling the structural parameters of the hexagonal mesoporous material within the above range, it can be ensured that the hexagonal mesoporous material is not easy to agglomerate, and the supported catalyst component prepared by using it as a carrier can improve the conversion rate of the reaction raw materials in the olefin polymerization reaction process. When the specific surface area of the hexagonal mesoporous material is less than 450m 2 / g and / or the pore volume is less than 0.5mL / g, the catalytic activity of the supported catalyst component prepared by using it as a carrier will be significantly reduced; when the specific surface area of the hexagonal mesoporous material is greater than 550m 2 / g and / or the pore volume is greater than 1.5mL / g, the supported catalyst component prepared by using it as a carrier is prone to agglomeration during the olefin polymerization reaction, thereby affecting the conversion rate of olefin monomers in the olefin polymerization reaction.
[0172] Preferably, the average pore size of the hexagonal mesoporous material is 4-12 nm, such as 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm and 12 nm, and any average pore size between any two average pore sizes, and the specific surface area is 480-520 m 2 / g, the pore volume is 0.5-1mL / g, the average particle size before ball milling is 0.8-8μm, and the average pore size after ball milling is 0.05-5μm, preferably 0.1-3μm, and more preferably 0.1-2, so that the hexagonal mesoporous material can be ensured to have the advantages of larger pore size, larger pore volume, and larger specific surface area, which is more conducive to the good dispersion of magnesium and titanium active components on the surface of the hexagonal mesoporous material, and further ensure that the polyolefin catalyst component prepared therefrom has excellent catalytic performance, thereby obtaining the beneficial effects of high olefin monomer conversion rate and good polymer particle morphology, low bulk density, excellent fluidity, etc.
[0173] Preferably, the average pore size of the polyolefin catalyst component is 4-15 nm, and the specific surface area is 450-500 m2 / g, the pore volume is 0.5-1mL / g, the average particle size is 0.5-20μm, preferably 0.8-15μm, and the particle size distribution value is 1.6-1.7.
[0174] Without being limited by any theory, it is believed that due to the pore size having a suitable size and a narrow distribution, the mesoporous material provides a considerable effective specific surface area, so that the catalyst component prepared therefrom can have a larger proportion of effective catalytic active centers, thereby showing high catalytic activity. Moreover, the mesoporous material has a suitable hardness, so it can be easily ground into a desired particle size for use as a filler in the slurry to be spray-dried. In addition, the chlorosilane treatment described in the present invention can change the surface properties of the mesoporous material, so that the treated mesoporous material is not easy to agglomerate and settle in the slurry to be spray-dried, thereby improving the stability and operability of the slurry to be spray-dried made of the treated mesoporous material.
[0175] In a fourth aspect, the present invention provides an olefin polymerization process comprising: a) polymerizing olefin monomers under polymerization conditions in the presence of the polyolefin catalyst component of the present invention and a cocatalyst to provide polyolefins; and b) recovering the polyolefins.
[0176] The polyolefin catalyst component of the present invention is used for the polymerization of olefin monomers to prepare polyolefins, including homopolymerization of ethylene or copolymerization of ethylene and other α-olefins, wherein the α-olefin can be selected from at least one of propylene, 1-butene, 1-hexene, 1-octene, 1-pentene, and 4-methyl-1-pentene.
[0177] According to the present invention, the reaction conditions of the polymerization reaction are not particularly limited and can be conventional olefin polymerization reaction conditions in the art. For example, the reaction can be carried out under an inert atmosphere, and the polymerization reaction conditions may include: a temperature of 10-100°C, a time of 0.5-5h, and a pressure of 0.1-2MPa; preferably, the polymerization reaction conditions may include: a temperature of 20-95°C, a time of 1-4h, and a pressure of 0.5-1.5MPa; further preferably, a temperature of 70-85°C, a time of 1-2h, and a pressure of 1-1.5MPa.
[0178] The pressure described in the present invention refers to the gauge pressure.
[0179] In the present invention, the polymerization reaction may be carried out in the presence of a solvent. The solvent that can be used in the polymerization reaction is not particularly limited, and it may be, for example, hexane.
[0180] In a specific embodiment, the supported polyolefin catalyst component can be a supported polyethylene catalyst component, and the polymerization reaction is an ethylene polymerization reaction. The ethylene polymerization method comprises: under the conditions of ethylene polymerization reaction, in the presence of a catalyst and a co-catalyst, polymerizing ethylene; preferably, the co-catalyst is an alkyl aluminum compound.
[0181] The cocatalyst that can be used in the method of the present invention can be any cocatalyst commonly used in the art. For example, the cocatalyst can be an alkyl aluminum compound shown in formula I:
[0182] AHr n X (3-n) Formula I
[0183] In Formula I, R can be a C1-C8, preferably a C1-C5 alkyl group; X can be a halogen atom, preferably a chlorine atom; and n is 1, 2 or 3.
[0184] Preferably, the C1-C8 alkyl group may be one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, tert-pentyl, n-hexyl, n-octyl, 2-ethylhexyl and neopentyl.
[0185] Specific examples of the alkylaluminum compound include, but are not limited to, trimethylaluminum, dimethylaluminum chloride, triethylaluminum, diethylaluminum chloride, tri-n-propylaluminum, di-n-propylaluminum chloride, tri-n-butylaluminum, tri-sec-butylaluminum, tri-tert-butylaluminum, di-n-butylaluminum chloride, and diisobutylaluminum chloride. Most preferably, the alkylaluminum compound is triethylaluminum.
[0186] The amount of the alkyl aluminum compound can also be selected according to conventional methods in the art. Generally, the molar ratio of the catalyst component to the alkyl aluminum compound can be 1:20-300.
[0187] In the present invention, the olefin polymerization method may further include separating the final reaction mixture after the polymerization reaction is completed, thereby obtaining polyolefin particle powder.
[0188] The present invention will be illustrated below by way of examples, but the present invention is not limited thereto.
[0189] In the following examples and comparative examples:
[0190] The triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene F127 was purchased from Aldrich Company, abbreviated as F127, and the molecular formula is EO 106 PO 70 EO 106 , the average molecular weight Mn is 12600;
[0191] The triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene P123 was purchased from Aldrich Company, abbreviated as P123, and the molecular formula is EO 20 PO 70 EO 20 , the substance with the registration number of Chemical Abstracts in the United States is 9003-11-6, and the average molecular weight Mn is 5800;
[0192] Polyoxyethylene-polyoxypropylene-polyoxyethylene Synperonic F108 was purchased from Fuka Company, and the molecular formula is EO 132 PO 60 EO 132 , average molecular weight Mn = 14600.
[0193] In the following examples and comparative examples, X-ray diffraction analysis was carried out on an X-ray diffractometer of model D8Advance purchased from Bruker AXS of Germany; scanning electron microscopy analysis was carried out on a scanning electron microscope of model XL-30 purchased from FEI of the United States; pore structure parameter analysis was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics of the United States, and the specific surface area and pore volume of the sample were calculated using the BET method; the particle size distribution SPAN value of the sample was measured on a Malvern laser particle size analyzer (Malvern, UK); the rotary evaporator was produced by IKA of Germany, model RVi0digital; the content of each component of the polyolefin catalyst component was measured on a wavelength dispersive X-ray fluorescence spectrometer of model Axios-Advanced purchased from PANalytical of the Netherlands; spray drying was carried out on a B-290 spray dryer purchased from Buchi of Switzerland.
[0194] The molecular weight distribution index (Mw / Mn) of the polyolefin powder was measured using a PL-GPC220 gel permeation chromatograph produced by Polymer Laboratories Ltd. of the United Kingdom according to the method specified in ASTM D6474-99.
[0195] The melt index of polyolefin is measured by the method specified in ASTM D1238-99.
[0196] The particle size of the granular materials was measured using a scanning electron microscope.
[0197] Example 1
[0198] This example is used to illustrate a polyolefin catalyst component and a method for preparing the same.
[0199] (1) Preparation of carrier
[0200] 1.0 g of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene P123 and 1.69 g of ethanol were added to 28 mL of acetic acid and sodium acetate buffer solution with a pH value of 4.4, and stirred at 15°C until polyoxyethylene-polyoxypropylene-polyoxyethylene P123 was completely dissolved; then 6 g of trimethylpentane was added to the above solution, and after stirring at 15°C for 8 hours, 2.13 g of tetramethoxysilane was added to the above solution, and after stirring at 15°C for 20 hours, the solution was transferred to a polytetrafluoroethylene-lined reactor, crystallized at 60°C for 24 hours, and then filtered, washed with deionized water, and dried to obtain the eggshell-shaped mesoporous material raw powder. The eggshell-like mesoporous material raw powder is calcined at 550°C in a muffle furnace for 24 hours to remove the template, thereby obtaining the eggshell-like mesoporous material A1 without the template and having a particle size between 3 and 22 μm; the eggshell-like mesoporous material A1 without the template is then calcined at 400°C for 10 hours under the protection of nitrogen for thermal activation treatment to remove the hydroxyl groups and residual moisture of the eggshell-like mesoporous material A1, thereby obtaining the thermally activated eggshell-like mesoporous material B1.
[0201] 10g of the above-mentioned heat-activated eggshell-like mesoporous material B1 was put into a 100ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was between 3 and 15mm, and the number was 30 (wherein the ratio of the number of large (diameter greater than 11mm), medium (diameter between 7 and 11mm) and small (diameter less than 7mm) grinding balls was approximately 1:2:3), and the ball mill was sealed. The temperature in the ball mill was 25°C and the rotation speed of the ball mill was 400r / min for 12h to obtain 10g of the ground eggshell-like mesoporous material carrier C1.
[0202] (2) Preparation of polyolefin catalyst components
[0203] 130 mL of tetrahydrofuran electron donor solvent was added to a reactor equipped with a stirring device that was purged with N2 and maintained in an N2 atmosphere. The reactor temperature was controlled to 30°C, and 5.3 g of magnesium dichloride and 1 mL of titanium tetrachloride were quickly added when stirring was turned on. The system temperature was adjusted to 70°C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. The solution was cooled to 50°C, and 6 g of eggshell-shaped mesoporous material carrier C1 was added to the solution containing magnesium dichloride and titanium tetrachloride, stirred for 2 hours, and a slurry to be sprayed with uniform concentration was obtained. Then, the obtained slurry to be sprayed was introduced into a spray dryer, and under N2 protection, the spray dryer air inlet temperature was controlled to be 140°C, the air outlet temperature was 105°C, and the carrier gas flow rate was 30L / s, and spray drying was performed to obtain a polyolefin catalyst component Cat-1.
[0204] The eggshell-like mesoporous material A1 and polyolefin catalyst Cat-1 were characterized by XRD, scanning electron microscopy, particle size analyzer and ASAP2020-M+C nitrogen adsorption instrument.
[0205] X-ray fluorescence analysis revealed that in the catalyst component Cat-1 obtained in this example, the content of magnesium was 11.17% by weight and the content of titanium was 2.55% by weight, calculated as the element.
[0206] Figure 1 The XRD spectrum of the eggshell-like mesoporous material A1 is shown in Figure 1. From the small-angle peaks in the XRD spectrum, it can be seen that the XRD spectrum of the eggshell-like mesoporous material carrier A1 has a 2D hexagonal pore structure that is unique to mesoporous materials.
[0207] Figure 2A is the pore size distribution curve of the eggshell-like mesoporous material A1. Figure 2B It is the nitrogen adsorption-desorption isotherm of the eggshell-like mesoporous material A1. It can be seen from the pore size distribution curve and the nitrogen adsorption-desorption isotherm spectrum that the eggshell-like mesoporous material A1 has a sharp IV type isotherm of capillary condensation rate, and the isotherm has an H1 hysteresis loop, which indicates that the sample has a uniform pore size distribution.
[0208] Figure 3A and Figure 3B These are scanning electron microscope images (SEM) of eggshell-like mesoporous material A1 (magnifications are 500K and 3000K respectively). It can be seen from the figure that the particle size of the sample is between 3-22μm.
[0209] Figure 3 is a SEM image of the polyolefin catalyst component Cat-1. As can be seen from the figure, the microscopic morphology of the polyolefin catalyst component Cat-1 is spherical, and the particle size is micrometer level, roughly in the range of 3-25μm.
[0210] Table 1 shows the pore structure parameters of eggshell-like mesoporous material A1 and polyolefin catalyst Cat-1.
[0211] Table 1
[0212]
[0213] It can be seen from the data in Table 1 that after the magnesium component and the titanium component are loaded on the eggshell-like mesoporous material A1, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the eggshell-like mesoporous material A1 during the loading reaction.
[0214] Example 2
[0215] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0216] (1) Preparation of carrier
[0217] 1.0 g of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene P123 and 1.84 g of ethanol were added to 28 mL of acetic acid and sodium acetate buffer solution with a pH value of 5, and stirred at 40°C until polyoxyethylene-polyoxypropylene-polyoxyethylene was completely dissolved; then 9.12 g of trimethylpentane was added to the above solution, and 3.04 g of tetramethoxysilane was added to the above solution after stirring at 40°C for 6 hours. After stirring at 40°C for 15 hours, the solution was transferred to a polytetrafluoroethylene-lined reactor, crystallized at 100°C for 10 hours, and then filtered, washed, and dried to obtain the original powder of the eggshell-like mesoporous material. The original powder of the eggshell-like mesoporous material was calcined in a muffle furnace at 600°C for 8 hours to remove the template agent, and the eggshell-like mesoporous material A2 with a particle size in the range of 3-12.5 μm without the template agent was obtained. Then, the eggshell-like mesoporous material A2 from which the template has been removed is calcined at 500° C. for 10 hours under the protection of nitrogen for thermal activation treatment to remove the hydroxyl groups and residual moisture of the eggshell-like mesoporous material A2, thereby obtaining a thermally activated eggshell-like mesoporous material B2.
[0218] Take 10g of the above-mentioned heat-activated eggshell-like mesoporous material B2 and put it into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding balls are made of agate, the diameter of the grinding balls is 3-15mm, the number is 30, and the speed of the ball mill is 300r / min. Close the ball mill. Ball mill the ball at a temperature of 30°C for 12h to obtain 10g of the ball-milled eggshell-like mesoporous material carrier C2.
[0219] (2) Preparation of polyolefin catalysts
[0220] 130 mL of tetrahydrofuran was added to a reactor equipped with a stirring device that was blown and maintained in an N2 atmosphere, and the reactor temperature was controlled to 30 ° C. 5.3 g of magnesium dichloride and 1 mL of titanium tetrachloride were quickly added when stirring was turned on, and the system temperature was adjusted to 70 ° C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. The solution was cooled to 50 ° C, 3 g of eggshell-shaped mesoporous material carrier C2 was added to the solution containing magnesium dichloride and titanium tetrachloride, and the reaction was stirred for 2 hours to obtain a uniform concentration of slurry to be sprayed. Then, the obtained slurry to be sprayed was introduced into a spray dryer, and under N2 protection, the spray dryer air inlet temperature was controlled to be 150 ° C, the air outlet temperature was 110 ° C, and the carrier gas flow rate was 40 L / s, and spray drying was performed to obtain a polyolefin catalyst component Cat-2.
[0221] The eggshell-like mesoporous material A2 and polyolefin catalyst Cat-2 were characterized by XRD, scanning electron microscopy, particle size analyzer and ASAP2020-M+C nitrogen adsorption instrument.
[0222] X-ray fluorescence analysis revealed that in the catalyst component Cat-2 obtained in this example, the content of magnesium was 15.39% by weight and the content of titanium was 3.12% by weight, calculated as the element.
[0223] Table 2 shows the pore structure parameters of the eggshell-like mesoporous material A2 and the polyolefin catalyst component Cat-2.
[0224] Table 2
[0225]
[0226] It can be seen from the data in Table 2 that after the magnesium component and the titanium component are loaded on the eggshell-like mesoporous material A2, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the eggshell-like mesoporous material A2 during the loading reaction.
[0227] Example 3
[0228] This example is used to illustrate the polyolefin catalyst and the preparation method thereof of the present invention.
[0229] (1) Preparation of carrier
[0230] 1.0 g of triblock copolymer polyoxyethylene-polyoxypropylene-polyoxyethylene P123 and 2.76 g of ethanol were added to 28 mL of acetic acid and sodium acetate buffer solution with a pH value of 3, and stirred at 15°C until polyoxyethylene-polyoxypropylene-polyoxyethylene was completely dissolved. Then 5.7 g of trimethylpentane was added to the above solution, and 2.13 g of tetramethoxysilane was added to the above solution after stirring at 15°C for 8 hours. After stirring at 40°C for 10 hours, the solution was transferred to a polytetrafluoroethylene-lined reactor, crystallized at 40°C for 40 hours, and then filtered, washed, and dried to obtain the original powder of the eggshell-like mesoporous material. The original powder of the eggshell-like mesoporous material was calcined in a muffle furnace at 450°C for 36 hours to remove the template agent, and the eggshell-like mesoporous material A3 with a particle size in the range of 5-16.2 μm was obtained. Then, the eggshell-like mesoporous material A3 from which the template has been removed is calcined at 700° C. for 8 h under the protection of nitrogen for thermal activation treatment to remove the hydroxyl groups and residual moisture of the eggshell-like mesoporous material A3, thereby obtaining a thermally activated eggshell-like mesoporous material B3.
[0231] 10g of the above-mentioned heat-activated eggshell-like mesoporous material B3 was put into a 100ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15mm, the number was 30, and the rotation speed of the ball mill was 550r / min. The ball mill was closed and ball milled for 10h at a temperature of 20°C in the ball mill to obtain 10g of the ball-milled eggshell-like mesoporous material carrier C3.
[0232] (2) Preparation of polyolefin catalyst components
[0233] 130 mL of tetrahydrofuran was added to a reactor equipped with a stirring device that was purged with N2 and maintained in an N2 atmosphere, and the reactor temperature was controlled to 40°C. When stirring was turned on, 5.3 g of magnesium dichloride and 1 mL of titanium tetrachloride were quickly added. The system temperature was adjusted to 70°C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. At 40°C, 4.5 g of eggshell-shaped mesoporous material carrier C3 was added to the solution containing magnesium dichloride and titanium tetrachloride, and the reaction was stirred for 2 hours to obtain a slurry to be sprayed with uniform concentration. Then, the obtained slurry to be sprayed was introduced into a spray dryer. Under N2 protection, the spray dryer air inlet temperature was controlled to be 135°C, the air outlet temperature was 105°C, the carrier gas flow rate was 30L / s, and spray drying was performed to obtain a polyolefin catalyst component Cat-3.
[0234] The eggshell-like mesoporous material A3 and the polyolefin catalyst component Cat-3 were characterized by XRD, scanning electron microscopy, particle size analyzer and ASAP2020-M+C nitrogen adsorption instrument.
[0235] X-ray fluorescence analysis revealed that in the catalyst component Cat-3 obtained in this example, the content of magnesium was 12.76% by weight and the content of titanium was 2.85% by weight, calculated as the element.
[0236] Table 3 shows the pore structure parameters of the eggshell-like mesoporous material A3 and the polyolefin catalyst component Cat-3.
[0237] Table 3
[0238]
[0239] It can be seen from the data in Table 3 that after the magnesium component and the titanium component are loaded on the eggshell-like mesoporous material A3, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the eggshell-like mesoporous material A3 during the loading reaction.
[0240] Example 4
[0241] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0242] The polyolefin catalyst component Cat-4 was prepared according to the method of Example 2, except that 6.87 g of diethoxymagnesium was used instead of 5.3 g of magnesium dichloride as the magnesium component, and 1.4 g of titanium trichloride was used instead of 1 mL of titanium tetrachloride as the titanium component.
[0243] The eggshell-like mesoporous material A4 and the polyolefin catalyst component Cat-4 were characterized by XRD, scanning electron microscopy and nitrogen adsorption instrument.
[0244] X-ray fluorescence analysis revealed that in the catalyst component Cat-4 obtained in this example, the content of magnesium was 21.43% by weight, and the content of titanium was 1.22% by weight, calculated on an element basis.
[0245] Table 4 shows the pore structure parameters of the eggshell-like mesoporous material A4 and the polyolefin catalyst component Cat-4.
[0246] Table 4
[0247]
[0248]
[0249] It can be seen from the data in Table 4 that after the magnesium component and the titanium component are loaded on the eggshell-like mesoporous material A4, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the eggshell-like mesoporous material A4 during the loading reaction.
[0250] Example 5
[0251] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention, wherein the mesoporous material is treated with chlorosilane.
[0252] (1) Preparation of carrier
[0253] Preparation and thermal activation of eggshell-like mesoporous material was as described in Example 1, giving thermally activated eggshell-like mesoporous material B1.
[0254] The ball milling treatment of the heat-activated eggshell-like mesoporous material B1 was carried out according to the procedure described in Example 1, except that 1 g of dichlorodimethoxysilane was added to the 100 ml ball milling jar together with the eggshell-like mesoporous material B1 to obtain a silane-modified, ball-milled eggshell-like mesoporous material carrier C5. The samples were characterized by contact angle and RDAX energy spectrum analysis. The characterization results showed that the contact angle of the untreated mesoporous material sample was 20°, and the contact angle of the mesoporous material after ball milling was 100°. Energy spectrum analysis showed that the untreated sample contained only Si and O, while the modified mesoporous material sample contained C, Cl, Si and O.
[0255] (2) Preparation of polyolefin catalyst components
[0256] Following the procedure described in Example 1, but using the mesoporous material support C5 instead of the mesoporous material support C1, a polyolefin catalyst component Cat-5 was prepared.
[0257] Comparative Example 1
[0258] This comparative example is used to illustrate a reference polyolefin catalyst component and a preparation method thereof.
[0259] (1) Preparation of carrier
[0260] Commercially available silica gel (TS610 from Cabot Corporation, with a particle size of 0.02-0.1 μm) was used as carrier D1. The silica gel carrier D1 was calcined at 400° C. for 10 h under nitrogen protection to remove hydroxyl groups and residual water, thereby obtaining a thermally activated silica gel carrier E1.
[0261] (2) Preparation of polyolefin catalyst components
[0262] A polyolefin catalyst component was prepared according to the method described in Example 1, except that the same weight of the activated silica gel carrier E1 was used instead of the eggshell-like mesoporous material carrier C1, thereby preparing a comparative catalyst component Cat-D-1.
[0263] X-ray fluorescence analysis revealed that in the catalyst component Cat-D-1 obtained in this example, the content of magnesium was 15.3% by weight and the content of titanium was 2.5% by weight, calculated as the element.
[0264] Comparative Example 2
[0265] This comparative example is used to illustrate a reference polyolefin catalyst component and a preparation method thereof.
[0266] The polyolefin catalyst component was prepared according to the method described in Example 1, except that the same weight of alumina carrier was used instead of eggshell-like mesoporous material carrier C1, thereby preparing carrier D2 and polyolefin catalyst component Cat-D-2, respectively.
[0267] X-ray fluorescence analysis revealed that in the catalyst component Cat-D-2 obtained in this example, the content of magnesium was 14.6% by weight and the content of titanium was 1.8% by weight, calculated as the element.
[0268] Comparative Example 3
[0269] This comparative example is used to illustrate a reference polyolefin catalyst component and a preparation method thereof.
[0270] The polyolefin catalyst was prepared according to the method described in Example 1, except that ball milling and spray drying were not used. Instead, the catalyst was directly filtered after the impregnation treatment, washed with n-hexane for 4 times, and dried at 75° C. to obtain the polyolefin catalyst component Cat-D-3.
[0271] X-ray fluorescence analysis revealed that in the catalyst Cat-D-3 obtained in this example, the content of magnesium was 11.14% by weight and the content of titanium was 1.12% by weight, calculated as the element.
[0272] Experimental Example 1
[0273] This example is used to illustrate a method for preparing polyethylene by polymerizing ethylene using the polyolefin catalyst component of the present invention.
[0274] The atmosphere in a 2L stainless steel high-pressure polymerization kettle was replaced with nitrogen and ethylene three times each. 1L hexane, 1mmol triethylaluminum and about 20mg of the catalyst component Cat-1 were added to the polymerization kettle, and then the temperature was raised to 85°C, hydrogen was added to 0.28MPa, and then the total pressure of the system was maintained at 1.0MPa with ethylene for polymerization reaction. After 2 hours of reaction, the addition of ethylene was stopped, the temperature was lowered, the pressure was released, and the polyethylene powder was taken out for weighing. The catalyst activity was calculated, and the molecular weight distribution index and melt index MI of the polyethylene powder were tested. 2.16 The results are listed in Table 5, as well as the efficiency of the catalyst.
[0275] Experimental Example 2-5
[0276] Ethylene was polymerized to prepare polyethylene according to the method described in Experimental Example 1, except that polyolefin catalyst components Cat-2 to Cat-5 were used instead of polyolefin catalyst component Cat-1. The molecular weight distribution index and melt index MI of the obtained polyethylene granules were 2.16 The efficiency of the catalysts is listed in Table 5.
[0277] Experimental Comparative Examples 1-3
[0278] Ethylene was polymerized to prepare polyethylene according to the method described in Experimental Example 1, except that polyolefin catalyst components Cat-D-1 to Cat-D-3 were used instead of polyolefin catalyst component Cat-1. The molecular weight distribution index and melt index MI of the obtained polyethylene granules were 2.16 The efficiency of the catalysts is listed in Table 5.
[0279] Table 5
[0280]
[0281] As can be seen from the result of Table 5, the polyolefin catalyst component prepared by adopting the eggshell-shaped mesoporous material carrier loaded titanium component and magnesium component has high catalytic activity, a larger melt index of the polymer powder, and a narrow molecular weight distribution of the polymer powder. Moreover, the polymer particles obtained when the catalyst component of the present invention is used for catalytic ethylene polymerization have good morphology and excellent fluidity. In addition, the method of the present invention is adopted to prepare a supported catalyst, and a spherical polyolefin catalyst component can be directly obtained in one step by spray drying, which is easy to operate.
[0282] Example 6
[0283] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0284] (1) Preparation of carrier
[0285] 2g of template F127 was added to a solution containing 37% by weight of hydrochloric acid (2.9g) and water (56g), and stirred at 40°C until F127 was completely dissolved; then 8.2g (0.04mol) of tetraethyl orthosilicate was added to the above solution, stirred at 40°C for 45min, and then the obtained solution was transferred to a polytetrafluoroethylene-lined reactor, crystallized at 100°C for 24h, then filtered and washed with deionized water 4 times, and then filtered and dried to obtain a mesoporous material powder with a cubic core structure. The mesoporous material powder with a cubic core structure was calcined in a muffle furnace at 400°C for 10h to remove the template, and obtain spherical mesoporous silica A6 with a particle size in the range of 3-9μm without the template. Then, the spherical mesoporous silica A6 from which the template has been removed is calcined at 400° C. for 10 h under the protection of nitrogen for thermal activation treatment to remove hydroxyl groups and residual moisture on the surface of the spherical mesoporous silica A6, thereby obtaining thermally activated spherical mesoporous silica B6.
[0286] 10 g of the above-mentioned heat-activated spherical mesoporous silica B6 was put into a 100 ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15 mm, the number was 30, and the rotation speed of the ball mill was 400 r / min. The ball mill was closed and ball milled for 12 h at a temperature of 25° C. in the ball mill to obtain the ball-milled spherical mesoporous silica carrier C6.
[0287] (2) Preparation of polyolefin catalyst components
[0288] 130 mL of tetrahydrofuran electron donor solvent was added to a reactor equipped with a stirring device that was blown through N2 and maintained in an N2 atmosphere, and the reactor temperature was controlled to 30 ° C. When stirring was turned on, 5.3 g of magnesium dichloride and 1 mL of titanium tetrachloride were quickly added. The system temperature was adjusted to 70 ° C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. The solution was cooled to 50 ° C, 6 g of spherical mesoporous silica carrier C6 was added to the solution containing magnesium dichloride and titanium tetrachloride, and the reaction was stirred for 2 hours to obtain a uniform concentration of spray slurry. Then, the obtained spray slurry was introduced into a spray dryer, and under N2 protection, the spray dryer air inlet temperature was controlled to be 140 ° C, the air outlet temperature was 105 ° C, and the carrier gas flow rate was 30 L / s, and spray drying was performed to obtain a polyolefin catalyst component Cat-6.
[0289] Spherical mesoporous silica A6 and polyolefin catalyst component Cat-6 were characterized by XRD, scanning electron microscopy, particle size analyzer and ASAP2020-M+C nitrogen adsorption instrument.
[0290] X-ray fluorescence analysis revealed that in the catalyst component Cat-6 obtained in this example, the content of magnesium was 12.54% by weight and the content of titanium was 2.95% by weight, calculated as the element.
[0291] Figure 5 The X-ray diffraction (XRD) spectrum of spherical mesoporous silica A6 is shown in Figure 1, wherein the abscissa is 2θ and the ordinate is intensity. From the small-angle peaks appearing in the XRD spectrum, it can be seen that the spherical mesoporous silica A6 has a cubic centered pore structure unique to the mesoporous material SBA-16.
[0292] Figure 6 This is a SEM scanning electron microscope image of spherical mesoporous silica A6. As can be seen from the image, the spherical mesoporous silica A6 is a microsphere with a particle size of 3-9 μm and good monodispersity.
[0293] Figure 7 This is a scanning electron microscope image of the polyolefin catalyst component Cat-6. As can be seen from the image, the polyolefin catalyst component Cat-6 is spherical and has a particle size of micrometer level.
[0294] Table 6 shows the pore structure parameters of spherical mesoporous silica A6 and polyolefin catalyst component Cat-6.
[0295] Table 6
[0296]
[0297] It can be seen from the data in Table 6 that after the magnesium component and the titanium component are loaded on the spherical mesoporous silica A6, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the spherical mesoporous silica A1 during the loading reaction.
[0298] Example 7
[0299] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0300] (1) Preparation of carrier
[0301] 2g of template F127 was added to a solution containing 37% by weight of hydrochloric acid (2.9g) and water (56g), and stirred at 40°C until F127 was completely dissolved; then 9.09g (0.044mol) of tetraethyl orthosilicate was added to the above solution and stirred at 60°C for 20h. Then, the obtained solution was transferred to a polytetrafluoroethylene-lined reactor, crystallized at 120°C for 20h, then filtered and washed with deionized water 4 times, and then filtered and dried to obtain a mesoporous material powder with a cubic core structure. The mesoporous material powder with a cubic core structure was calcined in a muffle furnace at 500°C for 15h to remove the template, and a spherical mesoporous silica A7 with a particle size of 4-8μm was obtained. Then, the spherical mesoporous silica A7 from which the template has been removed is calcined at 500° C. for 10 h under the protection of nitrogen for thermal activation treatment to remove hydroxyl groups and residual water on the surface of the spherical mesoporous silica A7, thereby obtaining thermally activated spherical mesoporous silica B7.
[0302] 10 g of the above-mentioned heat-activated spherical mesoporous silica B7 was put into a 100 ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15 mm, the number was 30, and the speed of the ball mill was 300 r / min. The ball mill was closed and ball milled at a temperature of 30° C. for 12 h to obtain the ball-milled spherical mesoporous silica carrier C7.
[0303] (2) Preparation of polyolefin catalyst components
[0304] 130 mL of tetrahydrofuran was added to a reactor equipped with a stirring device that was blown and maintained in an N2 atmosphere, and the reactor temperature was controlled to 30 ° C. When stirring was turned on, 5.3 g of magnesium dichloride and 1 mL of titanium tetrachloride were quickly added. The system temperature was adjusted to 70 ° C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. The solution was cooled to 50 ° C, and 3 g of spherical mesoporous silica carrier C7 was added to the solution containing magnesium dichloride and titanium tetrachloride, stirred for 2 hours, and a slurry to be sprayed with uniform concentration was obtained. Then, the obtained slurry to be sprayed was introduced into a spray dryer, and under N2 protection, the spray dryer air inlet temperature was controlled to be 150 ° C, the air outlet temperature was 110 ° C, and the carrier gas flow rate was 40 L / s, and spray drying was performed to obtain a polyolefin catalyst component Cat-7.
[0305] Spherical mesoporous silica A7 and polyolefin catalyst Cat-7 were characterized by XRD, scanning electron microscopy, particle size analyzer and ASAP2020-M+C nitrogen adsorption instrument.
[0306] X-ray fluorescence analysis revealed that in the catalyst component Cat-7 obtained in this example, the content of magnesium was 18.73% by weight and the content of titanium was 4.47% by weight, calculated on the basis of elements.
[0307] Table 7 shows the pore structure parameters of spherical mesoporous silica A7 and polyolefin catalyst component Cat-7.
[0308] Table 7
[0309]
[0310] It can be seen from the data in Table 7 that after the spherical mesoporous silica A7 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the spherical mesoporous silica A7 during the loading reaction.
[0311] Example 8
[0312] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0313] (1) Preparation of carrier
[0314] 2g of template F127 was added to a solution containing 37% by weight of hydrochloric acid (2.9g) and water (56g), and stirred at 40°C until F127 was completely dissolved; then, 7.44g (0.036mol) of tetraethyl orthosilicate was added to the above solution and stirred at 50°C for 24h. Then, the obtained solution was transferred to a polytetrafluoroethylene-lined reactor, crystallized at 90°C for 36h, then filtered and washed with deionized water 4 times, and then filtered and dried to obtain a mesoporous material powder with a cubic core structure. The mesoporous material powder with a cubic core structure was calcined in a muffle furnace at 500°C for 15h to remove the template, and a spherical mesoporous silica A8 with a particle size of 3.5-8.5μm was obtained. Then, the spherical mesoporous silica A8 from which the template has been removed is calcined at 700° C. for 8 h under the protection of nitrogen for thermal activation treatment to remove hydroxyl groups and residual water on the surface of the spherical mesoporous silica A8, thereby obtaining thermally activated spherical mesoporous silica B8.
[0315] 10 g of the above-mentioned heat-activated spherical mesoporous silica B8 was put into a 100 ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15 mm, the number was 30, and the rotation speed of the ball mill was 550 r / min. The ball mill was closed and ball milled for 10 h at a temperature of 20° C. in the ball mill to obtain the ball-milled spherical mesoporous silica carrier C8.
[0316] (2) Preparation of polyolefin catalysts
[0317] 130 mL of tetrahydrofuran was added to a reactor equipped with a stirring device that was blown and maintained in an N2 atmosphere, and the reactor temperature was controlled to 40 ° C. When stirring was turned on, 5.3 g of magnesium dichloride and 1 mL of titanium tetrachloride were quickly added. The system temperature was adjusted to 70 ° C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. At 40 ° C, 4.5 g of spherical mesoporous silica carrier C8 was added to the solution containing magnesium dichloride and titanium tetrachloride, stirred and reacted for 2 hours to obtain a uniform concentration of spray slurry. Then, the obtained spray slurry was introduced into a spray dryer, and under N2 protection, the spray dryer air inlet temperature was controlled to be 135 ° C, the air outlet temperature was 105 ° C, the carrier gas flow rate was 30 L / s, and spray drying was performed to obtain a polyolefin catalyst component Cat-8.
[0318] Spherical mesoporous silica A8 and polyolefin catalyst component Cat-8 were characterized by XRD, scanning electron microscopy, particle size analyzer and ASAP2020-M+C nitrogen adsorption instrument.
[0319] X-ray fluorescence analysis revealed that in the catalyst component Cat-8 obtained in this example, the content of magnesium was 13.09% by weight and the content of titanium was 3.60% by weight, calculated as the element.
[0320] Table 8 shows the pore structure parameters of spherical mesoporous silica A8 and polyolefin catalyst component Cat-8.
[0321] Table 8
[0322]
[0323] It can be seen from the data in Table 8 that after the spherical mesoporous silica A8 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the spherical mesoporous silica A8 during the loading reaction.
[0324] Example 9
[0325] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0326] The polyolefin catalyst component Cat-9 was prepared as described in Example 7, except that 6.87 g of diethoxymagnesium was used instead of 5.3 g of magnesium dichloride as the magnesium component, and 1.4 g of titanium trichloride was used instead of 1 mL of titanium tetrachloride as the titanium component.
[0327] Spherical mesoporous silica A9 and polyolefin catalyst Cat-9 were characterized by XRD, scanning electron microscopy and nitrogen adsorption.
[0328] X-ray fluorescence analysis revealed that in the catalyst component Cat-9 obtained in this example, the content of magnesium was 22.32% by weight, and the content of titanium was 1.25% by weight, calculated on the basis of elements.
[0329] Table 9 shows the pore structure parameters of spherical mesoporous silica A9 and polyolefin catalyst component Cat-9.
[0330] Table 9
[0331]
[0332] It can be seen from the data in Table 9 that after the spherical mesoporous silica A9 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the spherical mesoporous silica A9 during the loading reaction.
[0333] Example 10
[0334] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention, wherein the mesoporous material carrier is modified with chlorosilane.
[0335] (1) Preparation of carrier
[0336] The preparation and thermal activation of the spherical mesoporous silica material was as described in Example 6 to give a thermally activated spherical mesoporous silica material B10.
[0337] The ball milling treatment of the heat-activated mesoporous material B10 was carried out according to the procedure described in Example 6, except that 1g of dichlorodimethoxysilane was added to the 100ml ball milling jar together with the mesoporous material B10 to obtain a silane-modified, ball-milled spherical mesoporous silica material carrier C10. The sample was characterized by contact angle and RDAX energy spectrum analysis. The characterization results showed that the contact angle of the untreated mesoporous material sample was 21°, and the contact angle of the mesoporous material after ball milling was 102°. Energy spectrum analysis showed that the untreated sample contained only Si and O, while the modified mesoporous material sample contained C, Cl, Si and O.
[0338] (2) Preparation of polyolefin catalyst components
[0339] Following the procedure described in Example 6, but using the mesoporous material support C10 instead of the mesoporous material support C6, a polyolefin catalyst component Cat-10 was prepared.
[0340] Comparative Example 4
[0341] This comparative example is used to illustrate a reference polyolefin catalyst component and a preparation method thereof.
[0342] The polyolefin catalyst component was prepared according to the method of Example 6, except that spray drying and ball milling were not used. Instead, the mixture was directly filtered after the impregnation treatment, washed with n-hexane for 4 times, and dried at 75° C., thereby obtaining the polyolefin catalyst component Cat-D-4.
[0343] X-ray fluorescence analysis revealed that in the catalyst component Cat-D-4 obtained in this example, the content of magnesium was 11.2% by weight and the content of titanium was 1.3% by weight, calculated as the element.
[0344] Experimental Example 6
[0345] This example is used to illustrate the method for preparing polyethylene by ethylene polymerization using the polyolefin catalyst component of the present invention.
[0346] The atmosphere in a 2L stainless steel high-pressure polymerization kettle was replaced with nitrogen and ethylene three times each. 1L hexane, 1mmol triethylaluminum and about 20mg of the catalyst component Cat-6 were added to the polymerization kettle, and then the temperature was raised to 85°C, hydrogen was added to 0.28MPa, and then the total pressure of the system was maintained at 1.0MPa with ethylene for polymerization reaction. After 2 hours of reaction, the addition of ethylene was stopped, the temperature was lowered, the pressure was released, and the polyethylene powder was taken out for weighing. The catalyst activity was calculated, and the molecular weight distribution index and melt index MI of the polyethylene powder were tested. 2.16 The results are listed in Table 10, as well as the efficiency of the catalyst.
[0347] Experimental Examples 7-10
[0348] Ethylene was polymerized to prepare polyethylene according to the method described in Experimental Example 6, except that polyolefin catalyst components Cat-7 to Cat-10 were used instead of polyolefin catalyst component Cat-6. The molecular weight distribution and melt index MI of the obtained polyethylene granules were 2.16 The efficiency of the catalysts is listed in Table 10.
[0349] Experimental Comparative Example 4
[0350] Ethylene was polymerized to prepare polyethylene according to the method described in Experimental Example 6, except that polyolefin catalyst component Cat-D-4 was used instead of polyolefin catalyst Cat-6. The molecular weight distribution and melt index MI of the obtained polyethylene granules were 2.16 The efficiency of the catalysts is listed in Table 10.
[0351] Table 10
[0352]
[0353]
[0354] As can be seen from the result of Table 10, the polyolefin catalyst component prepared by adopting spherical mesoporous silica carrier loaded titanium component and magnesium component has high catalytic activity, and the melt index of polymer powder is larger, and the molecular weight distribution of polymer powder is narrow. And catalyst component of the present invention is used for the good polymer particle form that catalytic ethylene polymerization obtains, has excellent fluidity. In addition, adopt method of the present invention to prepare supported catalyst, can directly obtain spherical polyolefin catalyst component in one step by spray drying method, easy and simple to operate.
[0355] Embodiment 11
[0356] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0357] (1) Preparation of carrier
[0358] 4 g (0.0007 mol) of template P123 was added to a solution containing 37 wt% hydrochloric acid (16.4 mL) and water (128 mL), and stirred at 40°C until P123 was completely dissolved. After that, 8.86 g (0.042 mol) of tetraethyl orthosilicate was added to the above solution and stirred at 40°C for 24 h. Then, the obtained solution was transferred to a polytetrafluoroethylene-lined reactor, crystallized at 150°C for 24 h, then filtered and washed with deionized water 4 times, and then filtered and dried to obtain the original mesoporous material powder. The original mesoporous material powder was washed with ethanol under reflux conditions for 24 h, and the template was removed to obtain the mesoporous molecular sieve A11. Then, the product from which the template was removed was calcined at 400°C for 10 h under the protection of nitrogen for thermal activation treatment to remove the hydroxyl groups and residual water on the surface of the mesoporous material to obtain the thermally activated mesoporous material B11.
[0359] 10g of the above-mentioned heat-activated mesoporous material B11 was put into a 100ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15mm, the number was 30, and the speed of the ball mill was 400r / min. The ball mill was closed and ball milled for 12h at a temperature of 25°C in the ball mill to obtain the ball-milled mesoporous material carrier C11.
[0360] (2) Preparation of polyolefin catalyst components
[0361] 140 mL of tetrahydrofuran electron donor solvent was added to a reactor equipped with a stirring device that was purged with N2 and maintained in an N2 atmosphere. The reactor temperature was controlled to 30°C, and 6 g of magnesium dichloride and 1.1 mL of titanium tetrachloride were quickly added when stirring was turned on. The system temperature was adjusted to 70°C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. The solution was cooled to 50°C, 6.8 g of mesoporous material carrier C11 was added to the solution containing magnesium dichloride and titanium tetrachloride, and the reaction was stirred for 2 hours to obtain a slurry to be sprayed with uniform concentration. Then, the obtained slurry to be sprayed was introduced into a spray dryer, and under N2 protection, the spray dryer air inlet temperature was controlled to be 140°C, the air outlet temperature was 105°C, and the carrier gas flow rate was 30L / s, and spray drying was performed to obtain the polyolefin catalyst component Cat-11.
[0362] The mesoporous material carrier C11 and polyolefin catalyst component Cat-11 were characterized by XRD, scanning electron microscopy, particle size analyzer and nitrogen adsorption analyzer.
[0363] X-ray fluorescence analysis revealed that in the catalyst component Cat-11 obtained in this example, the content of magnesium was 12.34% by weight, and the content of titanium was 2.16% by weight, calculated on the basis of elements.
[0364] Figure 8 is an X-ray diffraction spectrum, wherein a is the XRD spectrum of mesoporous molecular sieve A11, the abscissa is 2θ, and the ordinate is intensity. It can be clearly seen from the XRD spectrum that mesoporous molecular sieve A11 has a diffraction peak in the small angle region, indicating that the mesoporous molecular sieve A11 has a two-dimensional ordered hexagonal pore structure unique to the mesoporous material SBA-15.
[0365] Fig. 9 This is a scanning electron microscope image of the polyolefin catalyst component Cat-11. As can be seen from the image, the microscopic morphology of the polyolefin catalyst component Cat-11 is spherical and the particle size is in the micron level.
[0366] Table 11 shows the pore structure parameters of the mesoporous material carrier C11 and the polyolefin catalyst component Cat-11.
[0367] Table 11
[0368]
[0369] It can be seen from the data in Table 11 that after the mesoporous material carrier C11 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the mesoporous material carrier C11 during the loading reaction.
[0370] Example 12
[0371] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0372] (1) Preparation of carrier
[0373] 4 g (0.0007 mol) of template P123 was added to a solution containing 37 wt% hydrochloric acid (16.4 mL) and water (128 mL), and stirred at 40°C until P123 was completely dissolved. After that, 10.9 g (0.0525 mol) of tetraethyl orthosilicate was added to the above solution and stirred at 40°C for 24 h. Then, the obtained solution was transferred to a polytetrafluoroethylene-lined reactor, crystallized at 180°C for 20 h, then filtered and washed with deionized water 4 times, and then filtered and dried to obtain the original mesoporous material powder. The original mesoporous material powder was washed with ethanol under reflux conditions for 24 h, and the template was removed to obtain the mesoporous molecular sieve material A12. Then, the product from which the template was removed was calcined at 500°C for 10 h under the protection of nitrogen for thermal activation treatment to remove the hydroxyl groups and residual water on the surface of the mesoporous material to obtain the thermally activated mesoporous material B12.
[0374] 10g of the above-mentioned heat-activated mesoporous material B12 was put into a 100ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15mm, the number was 30, and the speed of the ball mill was 300r / min. The ball mill was closed and ball milled for 12h at a temperature of 30°C in the ball mill to obtain the ball-milled mesoporous material carrier C12.
[0375] (2) Preparation of polyolefin catalyst components
[0376] 140 mL of tetrahydrofuran was added to a reactor equipped with a stirring device that was blown and maintained in an N2 atmosphere, and the reactor temperature was controlled to 30°C. When stirring was turned on, 6 g of magnesium dichloride and 1.1 mL of titanium tetrachloride were quickly added. The system temperature was adjusted to 70°C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. The solution was cooled to 50°C, 3.5 g of the mesoporous material carrier C12 was added to the solution containing magnesium dichloride and titanium tetrachloride, and the reaction was stirred for 2 hours to obtain a uniform concentration of the slurry to be sprayed. Then, the obtained slurry to be sprayed was introduced into a spray dryer, and under N2 protection, the spray dryer air inlet temperature was controlled to be 150°C, the air outlet temperature was 110°C, and the carrier gas flow rate was 40L / s, and spray drying was performed to obtain the polyolefin catalyst component Cat-12.
[0377] The mesoporous material carrier C2 and polyolefin catalyst component Cat-12 were characterized by XRD, scanning electron microscopy, particle size analyzer and nitrogen adsorption instrument.
[0378] X-ray fluorescence analysis revealed that in the catalyst component Cat-12 obtained in this example, the content of magnesium was 10.53% by weight and the content of titanium was 2.18% by weight, calculated as the element.
[0379] Table 12 shows the pore structure parameters of the mesoporous material carrier C12 and the polyolefin catalyst component Cat-12.
[0380] Table 12
[0381]
[0382] It can be seen from the data in Table 12 that after the mesoporous material carrier C12 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the mesoporous material carrier C12 during the loading reaction.
[0383] Embodiment 13
[0384] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0385] (1) Preparation of carrier
[0386] 4 g (0.0007 mol) of template P123 was added to a solution containing 37 wt% hydrochloric acid (16.4 mL) and water (128 mL), and stirred at 40°C until P123 was completely dissolved. After that, 7.27 g (0.035 mol) of tetraethyl orthosilicate was added to the above solution, stirred at 50°C for 20 h, and then the obtained solution was transferred to a polytetrafluoroethylene-lined reactor, crystallized at 175°C for 22 h, then filtered and washed with deionized water 4 times, and then filtered and dried to obtain the original mesoporous material powder. The original mesoporous material powder was washed with ethanol under reflux conditions for 24 h, and the template was removed to obtain the mesoporous molecular sieve material A13. Then, the product from which the template was removed was calcined at 700°C for 8 h under the protection of nitrogen for thermal activation treatment to remove the hydroxyl groups and residual moisture of the mesoporous material, and obtain the thermally activated mesoporous material B13.
[0387] 10g of the above-mentioned heat-activated mesoporous material B13 was put into a 100ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15mm, the number was 30, and the speed of the ball mill was 550r / min. The ball mill was closed and ball milled for 10h at a temperature of 20°C in the ball mill to obtain the ball-milled mesoporous material carrier C13.
[0388] (2) Preparation of polyolefin catalysts
[0389] 140 mL of tetrahydrofuran was added to a reactor equipped with a stirring device that was purged with N2 and maintained in an N2 atmosphere, and the reactor temperature was controlled to 40°C. When stirring was turned on, 6 g of magnesium dichloride and 1.1 mL of titanium tetrachloride were quickly added. The system temperature was adjusted to 70°C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. At 40°C, 5.1 g of the mesoporous material carrier C13 was added to the solution containing magnesium dichloride and titanium tetrachloride, and the reaction was stirred for 2 hours to obtain a slurry to be sprayed with uniform concentration. Then, the obtained slurry to be sprayed was introduced into a spray dryer. Under N2 protection, the spray dryer air inlet temperature was controlled to be 135°C, the air outlet temperature was 105°C, the carrier gas flow rate was 30L / s, and spray drying was performed to obtain the polyolefin catalyst component Cat-13.
[0390] The mesoporous material carrier C13 and polyolefin catalyst component Cat-13 were characterized by XRD, scanning electron microscopy, particle size analyzer and nitrogen adsorption analyzer.
[0391] X-ray fluorescence analysis revealed that in the catalyst component Cat-13 obtained in this example, the content of magnesium was 13.2% by weight, and the content of titanium was 2.95% by weight, calculated on the basis of elements.
[0392] Table 13 shows the pore structure parameters of the mesoporous material carrier C13 and the polyolefin catalyst component Cat-13.
[0393] Table 13
[0394]
[0395] It can be seen from the data in Table 13 that after the mesoporous material carrier C13 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the mesoporous material carrier C13 during the loading reaction.
[0396] Embodiment 14
[0397] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0398] The polyolefin catalyst component Cat-14 was prepared according to the method of Example 12, except that 1.4 g of titanium trichloride was used instead of 1.1 mL of titanium tetrachloride as the titanium component.
[0399] The mesoporous material carrier C14 and polyolefin catalyst component Cat-14 were characterized by XRD, scanning electron microscopy and nitrogen adsorption instrument.
[0400] X-ray fluorescence analysis revealed that in the catalyst component Cat-14 obtained in this example, the content of magnesium was 13.94% by weight, and the content of titanium was 2.22% by weight, calculated on the basis of elements.
[0401] Table 14 shows the pore structure parameters of the mesoporous material carrier C14 and the polyolefin catalyst component Cat-14.
[0402] Table 14
[0403]
[0404] It can be seen from the data in Table 14 that after the mesoporous material carrier C14 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the mesoporous material carrier C14 during the loading reaction.
[0405] Embodiment 15
[0406] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention, wherein the mesoporous material carrier is modified with chlorosilane.
[0407] (1) Preparation of carrier
[0408] The preparation and thermal activation of the mesoporous material were as described in Example 11, giving thermally activated mesoporous material B15.
[0409] The ball milling treatment of the heat-activated mesoporous material B15 was carried out according to the procedure described in Example 11, except that 1g of dichlorodimethoxysilane was added to the 100ml ball milling jar together with the mesoporous material B15 to obtain a silane-modified, ball-milled spherical mesoporous silica material carrier C15. The sample was characterized by contact angle and RDAX energy spectrum analysis. The characterization results showed that the contact angle of the untreated mesoporous material sample was 20°, and the contact angle of the mesoporous material after ball milling was 100°. Energy spectrum analysis showed that the untreated sample contained only Si and O, while the modified mesoporous material sample contained C, Cl, Si and O.
[0410] (2) Preparation of polyolefin catalyst components
[0411] Following the procedure described in Example 11, but using the mesoporous material support C15 instead of the mesoporous material support C11, a polyolefin catalyst component Cat-15 was prepared.
[0412] Comparative Example 5
[0413] This comparative example is used to illustrate a reference polyolefin catalyst component and a preparation method thereof.
[0414] A polyolefin catalyst was prepared according to the method of Example 11, except that spray drying and ball milling were not used. Instead, the catalyst was directly filtered after the impregnation treatment, washed with n-hexane for 4 times, and dried at 75° C., thereby obtaining a polyolefin catalyst component Cat-D-5.
[0415] X-ray fluorescence analysis revealed that in the catalyst component Cat-D-5 obtained in this example, the content of magnesium was 12.9% by weight and the content of titanium was 1.6% by weight, calculated as the element.
[0416] Experimental Example 11
[0417] This example is used to illustrate a method for preparing polyethylene by polymerizing ethylene using the polyolefin catalyst component of the present invention.
[0418] The atmosphere in a 2L stainless steel high-pressure polymerization kettle was replaced with nitrogen and ethylene three times each. 1L hexane, 1mmol triethylaluminum and about 20mg of the catalyst component Cat-11 were added to the polymerization kettle, and then the temperature was raised to 85°C, hydrogen was added to 0.28MPa, and then the total pressure of the system was maintained at 1.0MPa with ethylene for polymerization reaction. After 2 hours of reaction, the addition of ethylene was stopped, the temperature was lowered, the pressure was released, and the polyethylene powder was taken out for weighing. The catalyst activity was calculated, and the molecular weight distribution index and melt index MI of the polyethylene powder were tested. 2.16 The results are listed in Table 15, as well as the efficiency of the catalyst.
[0419] Experimental Examples 12-15
[0420] Ethylene polymerization was carried out according to the method of Experimental Example 11, except that polyolefin catalyst components Cat-12 to Cat-15 were used instead of polyolefin catalyst component Cat-11. The molecular weight distribution (Mw / Mn) and melt index MI of the obtained polyethylene granules were 2.16 And the efficiency of the catalyst is listed in Table 15.
[0421] Experimental Comparative Example 5
[0422] Ethylene polymerization was carried out according to the method of Experimental Example 11 to prepare polyethylene, except that polyolefin catalyst component Cat-D-5 was used instead of polyolefin catalyst component Cat-11. The molecular weight distribution (Mw / Mn), melt index MI 2.16 and catalyst efficiency of the obtained polyethylene granules are listed in Table 15.
[0423] Table 15
[0424]
[0425] As can be seen from the result of Table 15, the polyolefin catalyst prepared by adopting mesoporous material carrier loaded titanium component and magnesium component has high catalytic activity, and the melt index of polymer powder is larger, and the molecular weight distribution of polymer powder is narrow. And the polymer particles that catalyst component of the present invention obtains when being used for catalytic ethylene polymerization have good form and excellent fluidity. In addition, adopt method of the present invention to prepare loaded catalyst, can directly obtain spherical polyolefin catalyst in one step by spray drying method, easy and simple to operate.
[0426] Example 16
[0427] This example is used to illustrate a polyolefin catalyst component and a method for preparing the same.
[0428] (1) Preparation of carrier
[0429] 2g (1.4×10 -4 mol) template F108, 5.24 g (0.03 mol) of K2SO4 and 60 g of 2N hydrochloric acid solution were stirred at 38°C until F108 was completely dissolved.
[0430] 4.2 g (0.02 mol) of ethyl orthosilicate was added to the above solution, stirred at 38° C. for 15 min, and allowed to stand at 38° C. for 24 h for crystallization.
[0431] Then, 100 g of deionized water was added to the mixed solution to dilute it, followed by filtration and washing with deionized water for 4 times. Then, the raw powder of hexagonal mesoporous material having a cube-centered Im3m structure was obtained by suction filtration.
[0432] The hexagonal mesoporous material raw powder with a cube-centered Im3m structure obtained above was calcined at 400°C for 10 hours to remove the template agent, thereby obtaining the hexagonal mesoporous material A16. The product after the template agent was removed was then calcined at 400°C for 10 hours under the protection of nitrogen for thermal activation treatment to remove the hydroxyl groups and residual water on the surface of the hexagonal mesoporous material, thereby obtaining the thermally activated hexagonal mesoporous material B16.
[0433] 10g of the above-mentioned heat-activated hexagonal mesoporous material B16 was put into a 100ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15mm, the number was 30, and the speed of the ball mill was 400r / min. The ball mill was closed and ball milled for 12h at a temperature of 25°C in the ball mill to obtain the ball-milled hexagonal mesoporous material carrier C16.
[0434] (2) Preparation of polyolefin catalyst components
[0435] 130 mL of tetrahydrofuran electron donor solvent was added to a reactor equipped with a stirring device that was purged with N2 and maintained in an N2 atmosphere, and the reactor temperature was controlled to 30°C. 5.3 g of magnesium dichloride and 1 mL of titanium tetrachloride were quickly added when stirring was turned on. The system temperature was adjusted to 70°C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. The solution was cooled to 50°C, 6 g of hexagonal mesoporous material carrier C16 was added to the solution containing magnesium dichloride and titanium tetrachloride, and the reaction was stirred for 2 hours to obtain a uniform concentration of slurry to be sprayed. Then, the obtained slurry to be sprayed was introduced into a spray dryer, and under N2 protection, the spray dryer air inlet temperature was controlled to be 140°C, the air outlet temperature was 105°C, and the carrier gas flow rate was 30L / s, and spray drying was performed to obtain a polyolefin catalyst Cat-16.
[0436] The hexagonal mesoporous material carrier C16 and polyolefin catalyst component Cat-16 were characterized by XRD, scanning electron microscopy, particle size analyzer and nitrogen adsorption instrument.
[0437] X-ray fluorescence analysis revealed that in the catalyst component Cat-16 obtained in this example, the content of magnesium was 15.54% by weight and the content of titanium was 2.73% by weight, calculated as the element.
[0438] Fig.10It is the X-ray diffraction spectrum of the hexagonal mesoporous material carrier C16, wherein the abscissa is 2θ and the ordinate is intensity. It can be clearly seen from the XRD spectrum that the hexagonal mesoporous material carrier C16 has a diffraction peak (2θ=0.6°) of the (110) plane consistent with the cube-centered Im3m and a diffraction shoulder peak (2θ=1.2°) of the (200) plane in the small angle region. The diffraction peak intensity of the (110) plane is high and the peak shape is narrow, indicating that the hexagonal mesoporous material carrier C16 has a good long-range ordered structure, which is consistent with the XRD spectrum of FDU-6 mesoporous material reported in the literature (Chengzhong Yu, Bozhi Tian, Jie Fan, Galen D. Stucky, Dongyuan Zhao, J. Am. Chem. Soc. 2002, 124, 4556-4557). In addition, the position of the diffraction shoulder peak (2θ = 1.2°) of the (200) plane is completely different from that of the hexagonal or layered structure.
[0439] Fig.11A This is the nitrogen adsorption-desorption curve of the hexagonal mesoporous material carrier C16 (the horizontal axis is relative pressure, the unit is p / p0), Fig. 11B This is the pore size distribution diagram of the hexagonal mesoporous material carrier C16 (the horizontal axis is the pore size, the unit is 0.1 nm). From the pore size distribution diagram, it can be seen that the hexagonal mesoporous material carrier C16 has a narrow pore size distribution and the pores are very uniform. Fig.11A The nitrogen adsorption-desorption isotherm shows that the hexagonal mesoporous material carrier C16 is a typical IUPAC-defined type IV adsorption-desorption isotherm, and the sample has an H2-type hysteresis loop, proving that the hexagonal mesoporous material carrier C16 has a unique cubic cage-shaped mesoporous structure reported in the literature. The desorption branch between the relative partial pressure of 0.4-0.5 also shows that the material has a cage-like pore structure.
[0440] Fig.12 This is a transmission electron microscope image of the hexagonal mesoporous material carrier C16. Fig.12 The shape of the pores on the (100) crystal plane of the hexagonal mesoporous material carrier C16 can be clearly seen in the figure. It can be seen from the figure that all samples have a cube-centered Im3m structure.
[0441] Fig.13 This is a scanning electron microscope image of the hexagonal mesoporous material carrier C16. As can be seen from the image, the microscopic morphology of the hexagonal mesoporous material carrier C16 is hexagonal, and the particle size is at the micron level.
[0442] Fig.14 This is a scanning electron microscope image of the polyolefin catalyst component Cat-16. As can be seen from the image, the microscopic morphology of the polyolefin catalyst component Cat-16 is spherical and the particle size is at the micron level.
[0443] Table 16 shows the pore structure parameters of the hexagonal mesoporous material carrier C16 and the polyolefin catalyst Cat-16.
[0444] Table 16
[0445]
[0446] It can be seen from the data in Table 16 that after the hexagonal mesoporous material carrier C16 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the hexagonal mesoporous material carrier C16 during the loading reaction.
[0447] Embodiment 17
[0448] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0449] (1) Preparation of carrier
[0450] 1.46 g (1 × 10 -4 mol) template F108, 6.96 g (0.04 mol) K2SO4 and 60 g 2N hydrochloric acid solution were stirred at 38°C until F108 was completely dissolved.
[0451] 3.1 g (0.015 mol) of tetraethyl orthosilicate was added to the above solution, stirred at 38° C. for 15 min, and allowed to stand at 40° C. for 20 h for crystallization.
[0452] Then, 100 g of deionized water was added to the mixed solution to dilute it, followed by filtration and washing with deionized water for 4 times. Then, the raw powder of hexagonal mesoporous material having a cube-centered Im3m structure was obtained by suction filtration.
[0453] The hexagonal mesoporous material raw powder with a cube-centered Im3m structure obtained above was calcined at 600°C for 20 hours to remove the template agent, thereby obtaining the hexagonal mesoporous material A17. The product after the template agent was removed was then calcined at 500°C for 10 hours under the protection of nitrogen for thermal activation treatment to remove the hydroxyl group and residual moisture of the hexagonal mesoporous material, thereby obtaining the thermally activated hexagonal mesoporous material B17.
[0454] 10g of the above-mentioned heat-activated hexagonal mesoporous material B17 was put into a 100ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 3-15mm, the number was 30, and the speed of the ball mill was 300r / min. The ball mill was closed and ball milled at a temperature of 30°C for 12h to obtain the ball-milled hexagonal mesoporous material carrier C17.
[0455] (2) Preparation of polyolefin catalyst components
[0456] 130 mL of tetrahydrofuran was added to a reactor equipped with a stirring device that was purged with N2 and maintained in an N2 atmosphere, and the reactor temperature was controlled to 30°C. When stirring was turned on, 5.3 g of magnesium dichloride and 1 mL of titanium tetrachloride were quickly added. The system temperature was adjusted to 70°C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. The solution was cooled to 50°C, 3 g of hexagonal mesoporous material carrier C17 was added to the solution containing magnesium dichloride and titanium tetrachloride, and the reaction was stirred for 2 hours to obtain a slurry to be sprayed with uniform concentration. Then, the obtained slurry to be sprayed was introduced into a spray dryer, and under N2 protection, the spray dryer air inlet temperature was controlled to be 150°C, the air outlet temperature was 110°C, and the carrier gas flow rate was 40L / s, and spray drying was performed to obtain the polyolefin catalyst component Cat-17.
[0457] The hexagonal mesoporous material carrier C17 and polyolefin catalyst component Cat-17 were characterized by XRD, scanning electron microscopy, particle size analyzer and nitrogen adsorption instrument.
[0458] X-ray fluorescence analysis revealed that in the catalyst component Cat-17 obtained in this example, the content of magnesium was 8.79% by weight, and the content of titanium was 3.12% by weight, calculated on the basis of the elements.
[0459] Table 17 shows the pore structure parameters of the hexagonal mesoporous material carrier C17 and the polyolefin catalyst Cat-17.
[0460] Table 17
[0461]
[0462] It can be seen from the data in Table 17 that after the hexagonal mesoporous material carrier C17 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the hexagonal mesoporous material carrier C17 during the loading reaction.
[0463] Embodiment 18
[0464] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0465] (1) Preparation of carrier
[0466] 1.46 g (1 × 10 -4 mol) template F108, 3.48 g (0.02 mol) of K2SO4 and 60 g of 2N hydrochloric acid solution were stirred at 35°C until F108 was completely dissolved.
[0467] 3.1 g (0.015 mol) of tetraethyl orthosilicate was added to the above solution, stirred at 35° C. for 15 min, and allowed to stand at 50° C. for 18 h for crystallization.
[0468] Then, 100 g of deionized water was added to the mixed solution to dilute it, followed by filtration and washing with deionized water for 4 times. Then, the raw powder of hexagonal mesoporous material having a cube-centered Im3m structure was obtained by suction filtration.
[0469] The hexagonal mesoporous material powder with a cube-centered Im3m structure obtained above was calcined at 550°C for 24 hours to remove the template agent, thereby obtaining the hexagonal mesoporous material A18. The product after the template agent was removed was then calcined at 700°C for 8 hours under the protection of nitrogen for thermal activation treatment to remove the hydroxyl group and residual moisture of the hexagonal mesoporous material, thereby obtaining the thermally activated hexagonal mesoporous material B18.
[0470] Take 10g of the above-mentioned heat-activated hexagonal mesoporous material B18 and put it into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding balls are made of agate, the diameter of the grinding balls is 3-15mm, the number is 30, the ball mill speed is 550r / min, the ball mill is closed, and the temperature in the ball mill is 20℃ for 10h to obtain the ball-milled hexagonal mesoporous material carrier C18.
[0471] (2) Preparation of polyolefin catalysts
[0472] 130 mL of tetrahydrofuran was added to a reactor equipped with a stirring device that was purged with N2 and maintained in an N2 atmosphere, and the reactor temperature was controlled to 40°C. When stirring was turned on, 5.3 g of magnesium dichloride and 1 mL of titanium tetrachloride were quickly added. The system temperature was adjusted to 70°C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. At 40°C, 4.5 g of hexagonal mesoporous material carrier C18 was added to the solution containing magnesium dichloride and titanium tetrachloride, stirred for reaction for 2 hours, and a slurry to be sprayed with uniform concentration was obtained. Then, the obtained slurry to be sprayed was introduced into a spray dryer. Under N2 protection, the spray dryer air inlet temperature was controlled to be 135°C, the air outlet temperature was 105°C, the carrier gas flow rate was 30L / s, and spray drying was performed to obtain a polyolefin catalyst Cat-18.
[0473] The hexagonal mesoporous material carrier C18 and polyolefin catalyst component Cat-18 were characterized by XRD, scanning electron microscopy, particle size analyzer and nitrogen adsorption instrument.
[0474] X-ray fluorescence analysis revealed that in the catalyst component Cat-18 obtained in this example, the content of magnesium was 18.7% by weight and the content of titanium was 2.85% by weight, calculated on the basis of elements.
[0475] Table 18 shows the pore structure parameters of the hexagonal mesoporous material carrier C18 and the polyolefin catalyst component Cat-18.
[0476] Table 18
[0477]
[0478] It can be seen from the data in Table 18 that after the hexagonal mesoporous material carrier C18 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the hexagonal mesoporous material carrier C18 during the loading reaction.
[0479] Embodiment 19
[0480] This example is used to illustrate the polyolefin catalyst component and the preparation method thereof of the present invention.
[0481] The polyolefin catalyst Cat-19 was prepared according to the method of Example 17, except that 1.4 g of titanium trichloride was used instead of 1 mL of titanium tetrachloride as the titanium component.
[0482] The hexagonal mesoporous material carrier C19 and polyolefin catalyst component Cat-19 were characterized by XRD, scanning electron microscopy and nitrogen adsorption instrument.
[0483] X-ray fluorescence analysis revealed that in the catalyst component Cat-19 obtained in this example, the content of magnesium was 24.43% by weight, and the content of titanium was 1.22% by weight, calculated on the basis of elements.
[0484] Table 19 shows the pore structure parameters of the hexagonal mesoporous material carrier C19 and the polyolefin catalyst component Cat-19.
[0485] Table 19
[0486]
[0487] It can be seen from the data in Table 19 that after the hexagonal mesoporous material carrier C19 is loaded with the magnesium component and the titanium component, the specific surface area and the pore volume are reduced, which indicates that the magnesium component and the titanium component enter the interior of the hexagonal mesoporous material carrier C19 during the loading reaction.
[0488] Embodiment 20
[0489] This example is used to illustrate a polyolefin catalyst component and a method for preparing the same.
[0490] (1) Preparation of carrier
[0491] 2g (1.4×10 -4mol) template F108, 5.24 g (0.03 mol) of K2SO4 and 60 g of 2N hydrochloric acid solution were stirred at 38°C until F108 was completely dissolved.
[0492] 4.2 g (0.02 mol) of ethyl orthosilicate was added to the above solution, stirred at 38° C. for 15 min, and allowed to stand at 38° C. for 24 h for crystallization.
[0493] Then, 100 g of deionized water was added to the mixed solution to dilute it, followed by filtration and washing with deionized water for 4 times. Then, the raw powder of hexagonal mesoporous material having a cube-centered Im3m structure was obtained by suction filtration.
[0494] The hexagonal mesoporous material raw powder with a cube-centered Im3m structure obtained above was calcined at 400°C for 10 hours to remove the template agent, thereby obtaining the hexagonal mesoporous material A20. The product after the template agent was removed was then calcined at 400°C for 10 hours under the protection of nitrogen for thermal activation treatment to remove the hydroxyl group and residual moisture of the hexagonal mesoporous material, thereby obtaining the thermally activated hexagonal mesoporous material B20.
[0495] Take 10g of the above-mentioned thermally activated hexagonal mesoporous material B20 and 1 gram of dichlorodimethoxysilane and put them into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3-15mm, the number is 30, and the speed of the ball mill is 400r / min. The ball mill is closed and ball milled for 12h at a temperature of 25°C in the ball mill to obtain the ball-milled hexagonal mesoporous material carrier C20. The sample was characterized by contact angle and RDAX energy spectrum analysis. The characterization results show that the contact angle of the untreated sample is 20°, and the contact angle after ball milling is 100°. Energy spectrum analysis shows that the untreated sample contains only Si and O, while the modified sample contains C, Cl, Si and O.
[0496] (2) Preparation of polyolefin catalysts
[0497] 130 mL of tetrahydrofuran electron donor solvent was added to a reactor equipped with a stirring device that was purged with N2 and maintained in an N2 atmosphere, and the reactor temperature was controlled to 30°C. 5.3 g of magnesium dichloride and 1 mL of titanium tetrachloride were quickly added when stirring was turned on. The system temperature was adjusted to 70°C for constant temperature reaction for 4 hours to obtain a solution containing magnesium dichloride and titanium tetrachloride. The solution was cooled to 50°C, 6 g of hexagonal mesoporous material carrier C20 was added to the solution containing magnesium dichloride and titanium tetrachloride, and the reaction was stirred for 2 hours to obtain a uniform concentration of slurry to be sprayed. Then, the obtained slurry to be sprayed was introduced into a spray dryer, and under N2 protection, the spray dryer air inlet temperature was controlled to be 140°C, the air outlet temperature was 105°C, and the carrier gas flow rate was 30L / s, and spray drying was performed to obtain a polyolefin catalyst Cat-20.
[0498] Comparative Example 6
[0499] This comparative example is used to illustrate a reference polyolefin catalyst component and a preparation method thereof.
[0500] A polyolefin catalyst was prepared according to the method of Example 16, except that spray drying and ball milling were not used. Instead, the catalyst was directly filtered after the impregnation treatment, washed with n-hexane four times, and dried at 75° C. to obtain a polyolefin catalyst component Cat-D-6.
[0501] X-ray fluorescence analysis revealed that in the catalyst component Cat-D-6 obtained in this example, the content of magnesium was 13.6% by weight and the content of titanium was 1.5% by weight, calculated as the element.
[0502] Experimental Example 16
[0503] This example is used to illustrate a method for preparing polyethylene by polymerizing ethylene using the polyolefin catalyst component of the present invention.
[0504] In a 2L stainless steel high-pressure polymerization reactor, nitrogen and ethylene were replaced three times each, 1L hexane, 1mmol triethylaluminum and about 20mg catalyst component Cat-16 were added to the 2L stainless steel stirring reactor, and then the temperature was raised to 85°C, hydrogen was added to 0.28MPa, and then ethylene was used to maintain the total pressure of the system at 1.0MPa for polymerization reaction. After 2 hours of reaction, the addition of ethylene was stopped, the temperature was lowered, the pressure was released, the polyethylene powder was taken out and weighed, the catalyst activity was calculated, and the bulk density and melt index MI of the polyethylene powder were tested. 2.16 The results of the catalyst are listed in Table 20.
[0505] Experimental Examples 17-20
[0506] Ethylene polymerization was carried out according to the method of Experimental Example 16, except that polyolefin catalyst components Cat-17 to Cat-20 were used instead of polyolefin catalyst component Cat-16. The molecular weight distribution and melt index MI of the obtained polyethylene granules were 2.16 And the efficiency of the catalyst is listed in Table 20.
[0507] Experimental Comparative Example 6
[0508] Ethylene polymerization was carried out according to the method of Experimental Example 16, except that the polyolefin catalyst component Cat-D-6 was used instead of the polyolefin catalyst component Cat-16. The molecular weight distribution and melt index MI of the obtained polyethylene granules were 2.16 And the efficiency of the catalyst is listed in Table 20.
[0509] Table 20
[0510]
[0511] As can be seen from the result of Table 20, the polyolefin catalyst component prepared by adopting mesoporous material carrier loaded titanium component and magnesium component has high catalytic activity, and the melt index of polymer powder is larger, and the molecular weight distribution of polymer powder is narrow. And the polymer particles that catalyst component of the present invention obtains when being used for catalytic ethylene polymerization have good form and excellent fluidity. In addition, adopt method of the present invention to prepare supported catalyst, can directly obtain spherical polyolefin catalyst in one step by spray drying method, easy and simple to operate.
[0512] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A mesoporous material subjected to heat activation treatment, wherein the heat activation treatment of the mesoporous material is carried out at a temperature of 300-900° C. for a time of 3-48 h under an inert atmosphere, and wherein after the heat activation treatment, the mesoporous material is further subjected to a chlorosilane treatment and a ball milling treatment, wherein the chlorosilane treatment and the ball milling treatment are carried out separately or simultaneously, Wherein the mesoporous material is selected from the group consisting of: a) Mesoporous materials with a two-dimensional hexagonal pore structure, with an average pore size of 4-15 nm, 550-650 nm 2 / g specific surface area, and 0.5-1.5mL / g pore volume, b) Eggshell-like mesoporous materials with a two-dimensional hexagonal pore structure, which have a pore volume of 0.5-1.5 mL / g and a pore volume of 100-500 m 2 / g specific surface area, and an average pore size of 5-15nm; c) Spherical mesoporous silica with a cubic center structure, which has a diameter of 700-900 m 2 / g specific surface area, 0.5-1mL / g pore volume, and 1-5nm average pore diameter; and d) a hexagonal mesoporous material having a cubic cage-like pore structure, wherein the crystal structure has a cubic-centered Im3m structure, and the average pore size of the hexagonal mesoporous material is 4-15 nm, and the specific surface area is 450-550 m 2 / g, and the pore volume is 0.5-1.5mL / g.
2. The heat-activated mesoporous material of claim 1, having a contact angle of at least 40°. The thermally activated mesoporous material according to claim 1 , which has a contact angle of 50-150°.
4. The heat-activated mesoporous material of claim 1, wherein the chlorine-containing silane is selected from the group consisting of dichlorodimethoxysilane, monochlorotrimethoxysilane, dichlorodiethoxysilane and monochlorotriethoxysilane.
5. A method for preparing a polyolefin catalyst component, the method comprising the steps of: (i) providing a mesoporous material that has been subjected to a heat activation treatment, wherein the heat activation treatment of the mesoporous material is performed at a temperature of 300-900° C. for a time of 3-48 hours under an inert atmosphere, and wherein after the heat activation treatment, the mesoporous material is further subjected to a chlorosilane treatment and a ball milling treatment, wherein the chlorosilane treatment and the ball milling treatment are performed separately or simultaneously; (ii) under an inert atmosphere, the heat-activated mesoporous material (iia) is impregnated with a solution containing a magnesium component and then with a solution containing a titanium component, (iib) is impregnated with a solution containing a titanium component and then with a solution containing a magnesium component, or (iic) is co-impregnated with solutions containing both a titanium component and a magnesium component to obtain a slurry to be sprayed; and (iii) spray drying the slurry to be sprayed obtained from step (ii) to obtain a solid polyolefin catalyst component, Wherein the mesoporous material carrier is selected from the following group: a) Mesoporous materials with a two-dimensional hexagonal pore structure, with an average pore size of 4-15 nm, 550-650 nm 2 / g specific surface area, 0.5-1.5 mL / g pore volume, and 0.5-15 μ m average particle size; b) Eggshell-like mesoporous materials with a two-dimensional hexagonal pore structure, which have a pore volume of 0.5-1.5 mL / g and a pore volume of 100-500 m 2 / g specific surface area, 5-15nm average pore size, and 3-20μm average particle size; c) Spherical mesoporous materials with a cubic center structure, which have an average particle size of 2-9 μm, 700-900 μm 2 / g specific surface area, 0.5-1mL / g pore volume, and 1-5nm average pore diameter; and d) A hexagonal mesoporous material having a cubic cage-like pore structure, wherein the crystal structure has a cubic-centered Im3m structure, and the average pore size of the hexagonal mesoporous material is 4-15 nm, and the specific surface area is 450-550 m 2 / g, the pore volume is 0.5-1.5mL / g, and the average particle size is 0.5-10μm.
6. The method of claim 5, wherein the chlorine-containing silane is selected from the group consisting of dichlorodimethoxysilane, monochlorotrimethoxysilane, dichlorodiethoxysilane and monochlorotriethoxysilane.
7. The method of claim 5, wherein the treatment of the heat-activated mesoporous material with the chlorosilane is performed as follows: under an inert atmosphere, the heat-activated mesoporous material and the chlorosilane are ball-milled together in a ball mill.
8. The method of claim 5, wherein the mesoporous material carrier is a) a mesoporous material having a two-dimensional hexagonal pore structure, and the method is carried out as follows: (a) mixing and contacting a silicon source and an acid agent in the presence of a template, and sequentially crystallizing, filtering and drying the mixture obtained after the mixing and contacting to obtain a raw mesoporous material powder; (b) subjecting the raw mesoporous material powder to a template release agent treatment, a heat activation treatment and a ball milling treatment in sequence to obtain a treated mesoporous material carrier; (c) Under an inert atmosphere, the treated mesoporous material carrier is impregnated in a solution containing a magnesium component and a titanium component to obtain a slurry to be sprayed; and (d) spray drying the slurry to be sprayed to obtain a solid polyolefin catalyst component.
9. The method of claim 8, having at least one of the following features: - In step (a), the mixing contact conditions include: The temperature is 25-60℃, the time is more than 25min, and the pH is 1-6; - In step (a), the template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene EO 20 PO 70 EO 20 ; - In step (a), the acidic agent is at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrobromic acid; - In step (a), the silicon source is at least one of ethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, sodium orthosilicate and silica sol; - In step (a), the molar ratio of the template to the silicon source is 1:(10-90); - In step (a), the crystallization conditions include: temperature of 90-180°C and time of 10-40h; - In step (b), the process of the template release agent treatment includes: washing the raw mesoporous material powder with alcohol at 90-120°C for 10-40 hours; - In step (b), the ball milling conditions include: the ball milling jar speed is 100-800r / min, the temperature in the ball milling jar is 15-100°C, and the ball milling time is 0.1-100h; - in step (b), introducing a chlorine-containing silane modifier during the ball milling process; - In step (c), the impregnation conditions include: an impregnation temperature of 25-100°C and an impregnation time of 0.1-5h; - The amount of the treated mesoporous material carrier, magnesium component and titanium component is such that in the prepared polyolefin catalyst component, based on the total weight of the polyolefin catalyst component, the content of the treated mesoporous material carrier is 20-90% by weight; the content of the magnesium component in terms of magnesium element is 1-50% by weight; the content of the titanium component in terms of titanium element is 1-50% by weight; - In step (d), the spray drying conditions include: nitrogen atmosphere, air inlet temperature of 100-150°C, air outlet temperature of 100-120°C, and carrier gas flow rate of 10-50 L / s.
10. The method according to claim 8, wherein the amounts of the treated mesoporous material carrier, magnesium component and titanium component are such that in the prepared polyolefin catalyst component, based on the total weight of the polyolefin catalyst component, the content of the treated mesoporous material carrier is 30-70% by weight; the content of the magnesium component as magnesium element is 1-30% by weight, and the content of the titanium component as titanium element is 1-10% by weight.
11. The method of claim 5, wherein the mesoporous material carrier is b) an eggshell-like mesoporous material having a two-dimensional hexagonal pore structure, and the method is performed as follows: (a) under solution conditions, mixing a template with trimethylpentane and tetramethoxysilane to obtain a solution A, and sequentially crystallizing, filtering and drying the solution A to obtain an eggshell-shaped mesoporous material raw powder; (b) subjecting the eggshell-like mesoporous material raw powder to a template removal treatment, a heat activation treatment and a ball milling treatment to obtain an eggshell-like mesoporous material carrier; (c) in an inert atmosphere, impregnating the eggshell-shaped mesoporous material carrier in a solution containing a magnesium component and a titanium component to obtain a slurry to be sprayed; and (d) spray-drying the slurry to be sprayed to obtain a solid polyolefin catalyst component.
12. The method of claim 11, having at least one of the following features: - In step (a), the mixing contact conditions include: The temperature is 10-60°C, the time is 0.2-100h, and the pH value is 1-6; - The weight ratio of the template, the trimethylpentane and the tetramethoxysilane is 1: (1.2-20): (0.1-15); - The template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene EO 20 PO 70 EO 20 ; - The crystallization conditions include: temperature of 30-150°C and time of 4-72h; - In step (b), the process of the template release agent treatment comprises: calcining the eggshell-like mesoporous material raw powder at 300-600°C in an oxygen-containing atmosphere for 8-36h; - in step (b), introducing a chlorine-containing silane modifier during the ball milling process; - In step (c), the impregnation conditions include: an impregnation temperature of 25-100°C and an impregnation time of 0.1-5h; - The eggshell-like mesoporous material carrier, the magnesium component and the titanium component are used in such an amount that, in the prepared polyolefin catalyst component, the content of the eggshell-like mesoporous material carrier is 20-90% by weight, based on the total weight of the polyolefin catalyst component; the content of the magnesium component in terms of magnesium element is 1-50% by weight, and the content of the titanium component in terms of titanium element is 1-50% by weight; - In step (d), the spray drying conditions include: carried out under a nitrogen protective atmosphere, an air inlet temperature of 100-150°C, an air outlet temperature of 100-120°C, and a carrier gas flow rate of 10-50 L / s.
13. The method according to claim 11, wherein the amounts of the eggshell-like mesoporous material carrier, the magnesium component and the titanium component are such that in the prepared polyolefin catalyst component, based on the total weight of the polyolefin catalyst component, the content of the eggshell-like mesoporous material carrier is 30-70% by weight; the content of the magnesium component in terms of magnesium element is 1-30% by weight, and the content of the titanium component in terms of titanium element is 1-10% by weight.
14. The method of claim 5, wherein the mesoporous material support is c) a spherical mesoporous material having a cube-centered structure, and the method is performed as follows: (a) mixing and contacting a silicon source and an acid agent in the presence of a template, and sequentially crystallizing, filtering and drying the mixture obtained after the mixing and contacting to obtain a raw powder of a mesoporous material having a cubic center structure; (b) subjecting the raw mesoporous material powder to a template release treatment, a heat activation treatment and a ball milling treatment to obtain a spherical mesoporous material carrier; (c) in an inert atmosphere, impregnating the spherical mesoporous material carrier in a solution containing a magnesium component and a titanium component to obtain a slurry to be sprayed; and (d) spray-drying the slurry to be sprayed to obtain a solid polyolefin catalyst component.
15. The method of claim 14, having at least one of the following features: - In step (a), the molar ratio of the template to the silicon source is 1:200-300; - The template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene EO 106 PO 70 EO 106 ; - The silicon source comprises at least one of ethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, sodium orthosilicate and silica sol; - The mixed contact conditions include: The temperature is 25-60℃, the time is more than 25min, and the pH is 1-6; - The crystallization conditions include: temperature of 30-150°C and time of 10-72h; - In step (b), the process of the template release agent treatment comprises: calcining the raw powder of the mesoporous material having a cubic core structure for 8-20 hours at 300-600°C in an oxygen-containing atmosphere; - The ball milling conditions include: the rotation speed of the ball mill is 100-800 r / min, the temperature in the ball mill is 15-100°C, and the ball milling time is 0.1-100h; - in step (b), introducing a chlorine-containing silane modifier during the ball milling process; - In step (c), the impregnation conditions include: an impregnation temperature of 25-100°C and an impregnation time of 0.1-5h; - The amounts of the spherical mesoporous silica carrier, the magnesium component and the titanium component are such that in the prepared polyolefin catalyst component, based on the total weight of the polyolefin catalyst component, the content of the spherical mesoporous silica carrier is 20-90% by weight; the content of the magnesium component as magnesium element is 1-50% by weight; and the content of the titanium component as titanium element is 1-50% by weight; - In step (d), the spray drying conditions include: carried out under a nitrogen protective atmosphere, an air inlet temperature of 100-150°C, an air outlet temperature of 100-120°C, and a carrier gas flow rate of 10-50 L / s.
16. The method according to claim 14, wherein the amounts of the spherical mesoporous silica carrier, the magnesium component and the titanium component are such that in the prepared polyolefin catalyst component, based on the total weight of the polyolefin catalyst component, the content of the spherical mesoporous silica carrier is 30-70% by weight; the content of the magnesium component as magnesium element is 1-30% by weight, and the content of the titanium component as titanium element is 1-10% by weight.
17. The method of claim 5, wherein the mesoporous material carrier is d) a hexagonal mesoporous material having a cubic cage-like pore structure, and the method is performed as follows: (a) mixing and contacting a template, potassium sulfate, an acid agent and a silicon source, and crystallizing, filtering and drying the obtained mixture to obtain a hexagonal mesoporous material raw powder having a cubic center Im3m structure; (b) subjecting the raw powder of the hexagonal mesoporous material to a template release treatment, a heat activation treatment and a ball milling treatment in sequence to obtain a hexagonal mesoporous material carrier; (c) in the presence of an inert gas, impregnating the hexagonal mesoporous material carrier in a solution containing a magnesium component and a titanium component to obtain a slurry to be sprayed; and (d) spray-drying the slurry to be sprayed to obtain a solid polyolefin catalyst component.
18. The method of claim 17, having at least one of the following features: - In step (a), the molar ratio of the template, potassium sulfate and silicon source is 1:100-800:20-200; - The template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene EO 132 PO 60 EO 132 ; - The silicon source is at least one of ethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, sodium orthosilicate and silica sol; - The acidic agent is at least one of hydrochloric acid, sulfuric acid, nitric acid and hydrobromic acid; - The mixed contact conditions include: temperature of 25-60°C, time of 10-240 min, pH value of 1-7; - The crystallization conditions include: temperature of 25-60°C and time of 10-72h; - In step (b), the process of the template release agent treatment includes: calcining the hexagonal mesoporous material raw powder at 300-600°C in an oxygen-containing atmosphere for 8-20 hours; - The ball milling conditions include: the rotation speed of the ball mill is 100-800 r / min, the temperature in the ball mill is 15-100°C, and the ball milling time is 0.1-100h; - in step (b), introducing a chlorine-containing silane modifier during the ball milling process; - In step (c), the impregnation conditions include: an impregnation temperature of 25-100°C and an impregnation time of 0.1-5h; - The amounts of the hexagonal mesoporous material carrier, the magnesium component and the titanium component are such that in the prepared polyolefin catalyst component, based on the total weight of the polyolefin catalyst component, the content of the hexagonal mesoporous material carrier is 20-90% by weight; the content of the magnesium component as magnesium element is 1-50% by weight; and the content of the titanium component as titanium element is 1-50% by weight; - In step (d), the spray drying conditions include: carried out under a nitrogen protective atmosphere, an air inlet temperature of 100-150°C, an air outlet temperature of 100-120°C, and a carrier gas flow rate of 10-50 L / s.
19. The method according to claim 17, wherein the amounts of the hexagonal mesoporous material carrier, the magnesium component and the titanium component are such that in the prepared polyolefin catalyst component, based on the total weight of the polyolefin catalyst component, the content of the hexagonal mesoporous material carrier is 30-70% by weight; the content of the magnesium component as magnesium element is 1-30% by weight; and the content of the titanium component as titanium element is 1-10% by weight.
20. A polyolefin catalyst component obtained by the process according to any one of claims 5 to 19.
21. A polyolefin catalyst component, comprising a heat-activated mesoporous material carrier and a magnesium component, a titanium component and an optional electron donor component supported on the carrier, wherein before the magnesium component, the titanium component and the optional electron donor component are supported, the mesoporous material has been heat-activated at a temperature of 300-900° C. for 3-48 h under an inert atmosphere, and then further subjected to a chlorosilane treatment and a ball milling treatment, wherein the chlorosilane treatment and the ball milling treatment are carried out separately or simultaneously, Wherein the mesoporous material carrier is selected from the following group: A mesoporous material carrier having a two-dimensional hexagonal pore structure, which has an average pore size of 4-15nm, 550-650m 2 / g specific surface area, 0.5-1.5mL / g pore volume, and 0.05-5μm average particle size; An eggshell-shaped mesoporous material carrier having a two-dimensional hexagonal pore structure, which has a pore volume of 0.5-1.5 mL / g, 100-500 m 2 / g specific surface area, 5-15nm average pore size, and 0.05-5μm average particle size; Spherical mesoporous carrier with a cubic center structure, which has an average particle size of 0.05-5 μm, 700-900 m 2 / g specific surface area, 0.5-1mL / g pore volume, and 1-5nm average pore diameter; and A hexagonal mesoporous material carrier having a cubic cage-like pore structure, wherein the crystal structure has a cubic-centered Im3m structure, and the average pore size of the hexagonal mesoporous material carrier is 4-15 nm, and the specific surface area is 450-550 m 2 / g, the pore volume is 0.5-1.5mL / g, and the average particle size is 0.05-5μm.
22. The polyolefin catalyst component of claim 21, wherein the mesoporous material support has a contact angle of at least 40°.
23. The polyolefin catalyst component of claim 21, wherein the mesoporous material support has a contact angle of 50-150°.
24. The polyolefin catalyst component of claim 21, wherein the mesoporous material support has a contact angle of 70-130°.
25. The polyolefin catalyst component of claim 21, wherein the chlorine-containing silane modifier is selected from the group consisting of dichlorodimethoxysilane, monochlorotrimethoxysilane, dichlorodiethoxysilane, and monochlorotriethoxysilane.
26. The polyolefin catalyst component according to claim 21, wherein Based on the total weight of the polyolefin catalyst component, the content of the mesoporous material carrier is 20-90% by weight; the content of the magnesium component in terms of magnesium element is 1-50% by weight; and the content of the titanium component in terms of titanium element is 1-50% by weight.
27. The polyolefin catalyst component according to claim 21, wherein Based on the total weight of the polyolefin catalyst component, the content of the mesoporous material carrier is 30-70% by weight; the content of the magnesium component in terms of magnesium element is 1-30% by weight; and the content of the titanium component in terms of titanium element is 1-10% by weight.
28. The polyolefin catalyst component of claim 21, wherein - The mesoporous material carrier is a mesoporous material carrier having a two-dimensional hexagonal pore structure, and the average pore size of the polyolefin catalyst component is 4-15nm, and the specific surface area is 520-600m 2 / g, pore volume is 0.6-1.4mL / g, average particle size is 1-20μm, and particle size distribution value is 1.7-1.8; - The mesoporous material carrier is an eggshell-shaped mesoporous material carrier having a two-dimensional hexagonal pore structure, and the pore volume of the polyolefin catalyst is 0.5-1 mL / g and the specific surface area is 120-300 m 2 / g, average pore size is 7-12nm, average particle size is 3-25μm, and particle size distribution value is 0.85-0.95; - The mesoporous material carrier is a spherical mesoporous carrier with a cubic center structure, and the average particle size of the polyolefin catalyst is 3-25 μm, and the specific surface area is 700-800 m 2 / g, pore volume of 0.5-0.8mL / g, average pore diameter of 1.5-4.5nm, particle size distribution value of 0.85-0.95; or - The mesoporous material carrier is a hexagonal mesoporous material carrier having a cubic cage-like pore structure, and the average pore size of the polyolefin catalyst is 4-15 nm, and the specific surface area is 450-500 m 2 / g, the pore volume is 0.5-1mL / g, the average particle size is 0.5-20μm, and the particle size distribution value is 1.6-1.
7.
29. A process for the polymerization of olefins, the process comprising: a) polymerizing olefin monomers under polymerization conditions in the presence of a polyolefin catalyst component as claimed in any one of claims 20 to 28 and a cocatalyst to provide a polyolefin; and b) recovering the polyolefin.
Citation Information
Patent Citations
Process for producing ethylene polymers having reduced hexane extractable content
US5290745A
Application of metallocene catalyst-loaded hexagonal mesoporous material to olefinic polymerization
CN102040688A
Loaded metallocene catalyst and preparation method thereof
CN102453143A
Supported metallocene catalyst and its preparation method
CN102731687A
Alkene polymerization method
CN102952217A